Composite aluminum current collector, preparation method thereof, pole piece and electrochemical device

CN122907648APending Publication Date: 2026-10-13JIANGSU ENPACK COMPOSITE CURRENT COLLECTORS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611326560.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-29
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,整面辐照会造成基膜全域分子链发生交联或降解反应,虽能一定程度降低延伸率,却会导致基膜韧性与抗拉强度大幅衰减,成品抗弯折、抗拉伸性能劣化严重,反而影响复合集流体在后续加工和使用过程中的可靠性

Benefits of technology

本发明通过疏松铝种子层设于所述基膜的至少一侧表面,所述疏松铝种子层沿厚度方向贯设有多个针孔结构,所述疏松铝种子层的孔隙率为P,15%≤P≤40%;致密铝功能层设于所述疏松铝种子层远离所述基膜的一侧表面,且填充并覆盖所述针孔结构;其中,所述基膜上与所述针孔结构的对应位置具有离散点状损伤区,所述基膜的聚合物分子链在所述离散点状损伤区发生损伤。如此通过反向利用疏松铝层的针孔作为天然微掩模,通过针孔结构的对应位置形成离散点损伤区,在不显著损失基膜整体强度、不降低导电与耐蚀性能的前提下,精准降低复合集流体延伸率,解决涂布烘烤形变问题,同时工艺兼容现有卷绕蒸镀产线,易于规模化量产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907648A_ABST
    Figure CN122907648A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of composite aluminum current collector and preparation method, pole piece, electrochemical device, the composite aluminum current collector includes base film, loose aluminum seed layer and dense aluminum functional layer, loose aluminum seed layer is set on at least one side surface of the base film, the loose aluminum seed layer is along the thickness direction and is provided with multiple pinhole structure, the porosity of the loose aluminum seed layer is P, 15%≤P≤40%;Dense aluminum functional layer is set on the side surface of the loose aluminum seed layer away from the base film, and fill and cover the pinhole structure;Wherein, the base film has discrete point-like damage area with the corresponding position of the pinhole structure, and the polymer molecular chain of the base film is damaged in the discrete point-like damage area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to a composite aluminum current collector and its preparation method. Background Technology

[0002] Composite current collectors are functional thin films employing a "metal-polymer-metal" structure. A polymer material serves as the intermediate layer, with metal layers (such as copper or aluminum) deposited on both sides. Composite aluminum foil (MA) is used as the positive electrode current collector, and composite copper foil (MC) is used as the negative electrode current collector. They represent an upgraded alternative to traditional current collectors. Compared to traditional current collectors, composite current collectors offer significant advantages in improving battery safety, reducing weight, increasing energy density, and lowering costs, thus attracting widespread attention and application in the lithium-ion battery field.

[0003] However, the polymer base films (such as PET, PI, PP, etc.) in composite current collectors generally have high elongation at break, typically exceeding 100%. During subsequent processes such as battery electrode coating and high-temperature baking, the composite current collector is subjected to the combined effects of belt tension and thermal field, causing irreversible elongation deformation of the base film. This leads to problems such as electrode dimensional deviations and coating peeling, severely impacting battery production yield and electrochemical performance. Therefore, appropriately reducing the elongation of the composite current collector to match the process window of the coating and baking processes, while ensuring conductivity and base film strength, has become a pressing technical challenge in this field.

[0004] Currently, the mainstream solutions for controlling the elongation rate of composite current collectors in the industry mainly include the following: One approach is to modify the base film itself, adjusting the elongation rate of the base film through copolymerization modification or biaxial stretching process. However, the procurement cost of customized base films is high, and the overall tensile strength of the base film is significantly reduced when the elongation rate decreases, which can easily cause tape breakage problems in subsequent high-speed winding processing.

[0005] The second method is plasma surface modification, which involves bombarding the base film surface with plasma before coating to reduce elongation through recrystallization of surface molecular chains. However, the plasma treatment depth is extremely shallow (usually only at the nanometer level), so the modification effect is very limited. Furthermore, the uniformity of large-area treatment is poor, making it difficult to stably control the reduction in elongation.

[0006] Thirdly, there is the whole-surface ultraviolet irradiation modification. Current technologies often involve irradiating the entire base film with ultraviolet light before coating to improve the interfacial adhesion between the metal layer and the base film. However, whole-surface irradiation can cause cross-linking or degradation reactions in the molecular chains of the base film. Although it can reduce the elongation to a certain extent, it will lead to a significant decrease in the toughness and tensile strength of the base film. The bending and tensile properties of the finished product will be severely deteriorated, which will affect the reliability of the composite current collector in subsequent processing and use.

[0007] In summary, existing technical solutions are all insufficient to maintain the high strength and high toughness of the base film while effectively reducing the elongation rate. There is an urgent need to develop a new solution that balances elongation rate control and mechanical property retention.

[0008] The above content is only used to help understand the technical solution of the present invention and does not represent an admission that the above content is prior art. Summary of the Invention

[0009] The main objective of this invention is to provide a composite aluminum current collector and its preparation method, electrode, and electrochemical device, aiming to solve the aforementioned technical problems in the prior art.

[0010] To achieve the above objectives, the present invention provides a composite aluminum current collector, the composite aluminum current collector comprising: Base film; A loose aluminum seed layer is disposed on at least one side surface of the base film. The loose aluminum seed layer has a plurality of pinhole structures penetrating along the thickness direction. The porosity of the loose aluminum seed layer is P, where 15% ≤ P ≤ 40%. A dense aluminum functional layer is disposed on the side surface of the loose aluminum seed layer away from the base film, and fills and covers the pinhole structure; The base film has discrete point-like damage regions at positions corresponding to the pinhole structures, and the polymer molecular chains of the base film are damaged in these discrete point-like damage regions.

[0011] Preferably, in the composite aluminum current collector, the pore size of the pinhole structure is D, the thickness of the loose aluminum seed layer is H1, and 0.5:1≤H1 / D≤2:1.

[0012] Preferably, in the composite aluminum current collector, the thickness of the dense aluminum functional layer is H2, where 50nm ≤ H2 ≤ 200nm.

[0013] Preferably, in the composite aluminum current collector, 0.5μm≤D≤5μm; and / or, 10nm≤H1≤500nm.

[0014] Preferably, in the composite aluminum current collector, the material of the base film is one or more of polyethylene terephthalate, polyimide, polypropylene, and polybutylene terephthalate; And / or, The thickness of the base film is H3, where 4μm≤H3≤12μm.

[0015] Preferably, in the composite aluminum current collector, the loose aluminum seed layer has a gradient pore structure along the thickness direction. The loose aluminum seed layer includes a bottom layer close to the base film and an upper layer connected to the bottom layer. The porosity of the bottom layer is greater than that of the upper layer, and the pore size of the pinhole structure located in the bottom layer is greater than that of the pinhole structure located in the upper layer.

[0016] Preferably, in the composite aluminum current collector, the thickness of the upper layer accounts for 60%-70% of the thickness of the loose aluminum seed layer; and / or, The aperture of the pinhole structure located at the bottom layer is D1, and the aperture of the pinhole structure located at the top layer is D2, where 0.8μm≤D1≤6μm and 0.3μm≤D2≤2μm.

[0017] To achieve the above objectives, the present invention provides a method for preparing a composite aluminum current collector, the method comprising: Provide base film; A loose aluminum seed layer is formed on at least one surface of the base film. The loose aluminum seed layer has a plurality of pinhole structures penetrating along the thickness direction. The porosity of the loose aluminum seed layer is P, where 15% ≤ P ≤ 40%. The base film with the loose aluminum seed layer is irradiated with ultraviolet light. The ultraviolet light passes through the pinhole structure and irradiates the surface of the base film, causing discrete point-like damage areas to be formed on the surface of the base film corresponding to the position of the pinhole structure. The polymer molecular chains in the discrete point-like damage areas are damaged. A dense aluminum functional layer is formed on the surface of the loose aluminum seed layer away from the base film, so that the dense aluminum functional layer fills and covers the pinhole structure.

[0018] Preferably, in the preparation method of the composite aluminum current collector, the wavelength of the ultraviolet light is L, the irradiation dose is S, 200nm≤L≤380nm, and 50mJ / cm². 2 ≤S≤500mJ / cm 2 .

[0019] Preferably, in the preparation method of the composite aluminum current collector, the pore size of the pinhole structure is D, the thickness of the loose aluminum seed layer is H1, 0.5μm≤D≤5μm, 10nm≤H1≤500nm; Preferably, in the method for preparing the composite aluminum current collector, forming a loose aluminum seed layer on at least one side surface of the base film includes: In a vacuum environment with a first preset vacuum level, a loose aluminum seed layer is formed on at least one side surface of the base film by evaporation at a first preset evaporation rate, so that the loose aluminum seed layer forms the pinhole structure, and the first preset evaporation rate is v1, 8nm / s≤v1≤15nm / s; And / or, 0.5:1≤H1 / D≤2:1; And / or, the loose aluminum seed layer has a gradient pore structure along the thickness direction, the loose aluminum seed layer includes a bottom layer close to the base film and an upper layer connected to the bottom layer, the porosity of the bottom layer is greater than the porosity of the upper layer, the pore size of the pinhole structure located in the bottom layer is greater than the pore size of the pinhole structure located in the upper layer, the thickness of the upper layer accounts for 60%-70% of the thickness of the loose aluminum seed layer, the pore size of the pinhole structure located in the bottom layer is D1, the pore size of the pinhole structure located in the upper layer is D2, 0.8μm≤D1≤6μm, 0.3μm≤D2≤2μm.

[0020] Preferably, in the method for preparing the composite aluminum current collector, in the step of irradiating the base film with the loose aluminum seed layer using ultraviolet light, wherein the ultraviolet light passes through the pinhole structure to irradiate the surface of the base film, The ultraviolet light includes ultraviolet light in the deep ultraviolet band and ultraviolet light in the near ultraviolet band. The wavelength of the deep ultraviolet band is L1, and the wavelength of the near ultraviolet band is L2. 200nm≤L≤280nm, 315nm≤L≤380nm. And / or, the ultraviolet light is set at a preset tilt angle to the transport plane of the base film, and multiple sets of ultraviolet light sources are provided, which are arranged alternately along the transport direction of the base film. The preset tilt angle is A, 15°≤A≤45°. And / or, the irradiation cavity containing the ultraviolet light irradiation is filled with oxygen and inert gas, wherein the volume fraction of oxygen and inert gas is 0.1%-5%.

[0021] Preferably, in the method for preparing the composite aluminum current collector, the step of forming a dense aluminum functional layer on the surface of the loose aluminum seed layer away from the base film includes: In a vacuum environment with a second preset vacuum level, a dense aluminum functional layer is deposited on the surface of the loose aluminum seed layer away from the base film at a second preset evaporation rate, wherein the second preset evaporation rate is v2, 1nm / s≤v2≤5nm / s; And / or, The thickness of the dense aluminum functional layer is H2, where 50nm ≤ H2 ≤ 200nm.

[0022] To achieve the above objectives, the present invention provides an electrode sheet comprising the above-described composite aluminum current collector or a composite aluminum current collector prepared by the above-described preparation method.

[0023] To achieve the above objectives, the present invention provides an electrochemical device comprising the aforementioned electrode.

[0024] The present invention has at least the following beneficial effects: This invention utilizes a loose aluminum seed layer disposed on at least one side surface of a base film. This loose aluminum seed layer has multiple pinhole structures penetrating along its thickness direction, and its porosity is P, 15% ≤ P ≤ 40%. A dense aluminum functional layer is disposed on the side surface of the loose aluminum seed layer away from the base film, filling and covering the pinhole structures. The base film has discrete point-like damage regions corresponding to the pinhole structures, where the polymer molecular chains of the base film are damaged. By using the pinholes of the loose aluminum layer as a natural micromask, discrete point-like damage regions are formed at the corresponding positions of the pinhole structures. This precisely reduces the elongation of the composite current collector without significantly sacrificing the overall strength of the base film or reducing its conductivity and corrosion resistance, thus solving the coating and baking deformation problem. Simultaneously, the process is compatible with existing roll-to-roll evaporation lines and is easily mass-produced. Attached Figure Description

[0025] Figure 1 A schematic diagram of the composite aluminum current collector provided by the present invention; Figure 2 for Figure 1 Cross-sectional view of the composite aluminum current collector along AA; Figure 3 A flowchart illustrating the preparation method of the composite aluminum current collector provided by this invention.

[0026] 1-Base film, 2-Loose aluminum seed layer, 21-Pinhole structure, 3-Dense aluminum functional layer.

[0027] The objectives, features, and advantages of this invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0028] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. The present invention will be described in detail below with reference to the accompanying drawings and embodiments. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of the present invention can be combined with each other.

[0029] In this embodiment of the invention, the term "and / or" describes the relationship between associated objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The character " / " generally indicates that the preceding and following associated objects have an "or" relationship.

[0030] It should be noted that the terms "first," "second," etc., in the specification, claims, and drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence.

[0031] In this embodiment of the invention, the term "multiple" refers to two or more, and other quantifiers are similar.

[0032] In this invention, unless otherwise stated, directional terms such as "upper," "lower," "top," and "bottom" are generally used in relation to the direction shown in the accompanying drawings, or in relation to the vertical, perpendicular, or gravitational direction of the component itself; similarly, for ease of understanding and description, "inner" and "outer" refer to the inner and outer contours of each component itself, but the above directional terms are not intended to limit this invention.

[0033] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the various embodiments of the present invention will be described in detail below with reference to the accompanying drawings. However, those skilled in the art will understand that many technical details are presented in the embodiments of the present invention to facilitate a better understanding of the invention. However, the technical solutions claimed in the present invention can be implemented even without these technical details and various variations and modifications based on the following embodiments. The division of the following embodiments is for ease of description and should not constitute any limitation on the specific implementation of the present invention. The various embodiments can be combined with and referenced by each other without contradiction.

[0034] This invention provides a composite aluminum current collector; please refer to [link / reference]. Figure 1 and Figure 2 The composite aluminum current collector includes a base film 1, a loose aluminum seed layer 2, and a dense aluminum functional layer 3. The loose aluminum seed layer 2 is disposed on at least one side surface of the base film 1, and the loose aluminum seed layer 2 has a plurality of pinhole structures 21 penetrating along the thickness direction. The porosity of the loose aluminum seed layer 2 is P, 15%≤P≤40%. The dense aluminum functional layer 3 is disposed on the side surface of the loose aluminum seed layer 2 away from the base film 1, and fills and covers the pinhole structures 21. The base film 1 has discrete point-like damage areas at positions corresponding to the pinhole structures 21, and the polymer molecular chains of the base film 1 are damaged in the discrete point-like damage areas.

[0035] The present invention sets a loose aluminum seed layer 2 with 15%≤P≤40% and has multiple pinhole structures 21 penetrating along the thickness direction. Discrete point-like damage areas are formed on the base film 1 at the corresponding positions of the pinhole structures 21. The overall elongation of the base film 1 is effectively reduced by the breakage or cross-linking of polymer molecular chains in the discrete point-like damage areas, while the corresponding positions of non-pinhole structures 21 on the base film 1 are unaffected, and the original mechanical strength is completely preserved.

[0036] In some embodiments, the discrete point-like damage regions on the base film 1 corresponding to the pinhole structure 21 are typically formed by ultraviolet (UV) irradiation. Specifically, UV light selectively passes through the pinhole structure 21 of the loose aluminum seed layer 2 and irradiates the surface of the base film 1, forming discrete point-like damage regions on the base film 1 at the positions corresponding to the pinhole structure 21. In some embodiments, the pore size D of the pinhole structure 21 is 0.5 μm ≤ D ≤ 5 μm. Within this pore size range, UV light exhibits a significant diffraction effect, forming a modified light spot slightly larger than the pinhole pore size on the surface of the base film 1, ensuring the effectiveness of the single-pore modification coverage area. Simultaneously, the pinhole structure 21 within this pore size range is on the same order of magnitude as the UV wavelength (200 nm ~ 380 nm), causing multiple reflections of the light within the pinhole walls, forming a microcavity focusing effect to compensate for the light intensity attenuation along the path, ensuring sufficient modification energy is obtained by the surface of the base film 1. As a result, the polymer molecular chains in the discrete point-like damage area break or cross-link, and the mobility of the molecular chains is effectively restricted, thereby reducing the overall elongation of the base film 1 on a macroscopic level. Meanwhile, the non-pinhole corresponding positions on the base film 1 are not subjected to irradiation, and the original mechanical strength is completely preserved.

[0037] It should be noted that when the diameter of the pinhole structure 21 is less than 0.5 μm, the ultraviolet diffraction effect is limited (wavelength to aperture ratio < 1), resulting in extremely low optical coupling efficiency; when it is greater than 5 μm, the masking effect is insufficient, and the single-hole modification area is too large, approaching the effect of full-surface irradiation. Therefore, by controlling the aperture D of the pinhole structure 21 within the range of 0.5 μm ≤ D ≤ 5 μm, the present invention can achieve the optimal balance between ultraviolet diffraction efficiency and mask confinement effect, thereby maximizing the retention of the strength of the base film 1 while effectively reducing the elongation of the composite aluminum current collector. In some other embodiments, D can also be 1 μm, 2 μm, or 3 μm.

[0038] The thickness of the loose aluminum seed layer is H1, and in some embodiments, 10nm ≤ H1 ≤ 500nm. When the thickness of the loose aluminum seed layer 2 is less than 10nm, it is discontinuous, resulting in insufficient pinhole masking; when it is greater than 500nm, the aspect ratio H1 / D is too large (>2:1), causing severe attenuation of ultraviolet light reflection on the inner wall of the pinhole, leading to insufficient modification energy on the surface of the base film 1. Therefore, in this invention, by controlling the thickness H1 of the loose aluminum seed layer 2 within the range of 10nm ≤ H1 ≤ 500nm, the integrity and functionality of the pinhole structure 21 as a natural micromask for ultraviolet light can be ensured, while also ensuring that ultraviolet light can effectively penetrate the pinhole to reach the surface of the base film 1 for sufficient modification. Furthermore, the thickness H1 of the loose aluminum seed layer 2 determines the aspect ratio (H1 / D) of the pinhole structure 21, which directly affects the transmission efficiency of ultraviolet light within the pinhole channel. When H1 is controlled within the range of 10nm to 500nm, and the pore size D is 0.5μm to 5μm, the aspect ratio of the pinhole can be maintained within a reasonable range of 0.5:1 to 2:1. Within this aspect ratio range, the number of reflections of ultraviolet light on the inner wall of the pinhole is moderate, and the light intensity attenuation is controllable, enabling effective transmission to the surface of the base film 1 and providing sufficient modification energy. In other embodiments, H1 can also be 50nm, 100nm, 200nm, or 300nm.

[0039] When the porosity of the loose aluminum seed layer 2 is below 15%, the modified area is insufficient, resulting in limited reduction in elongation. When it is above 40%, the modified area of ​​the base film 1 is too large, causing the strength retention rate to drop below 80%. Therefore, in this invention, by controlling the porosity P of the loose aluminum seed layer 2 within the range of 15% ≤ P ≤ 40%, the optimal balance between the modified area of ​​the base film 1 by ultraviolet light and the strength retention rate of the base film 1 can be ensured. This effectively reduces the elongation of the composite aluminum current collector while ensuring that the base film 1 has sufficient processing strength. Specifically, the porosity P determines the areal density of the pinhole structure 21 in the loose aluminum seed layer 2, i.e., the number of discrete points that ultraviolet light can penetrate and act on the base film 1. When 15% ≤ P ≤ 40%, the pinholes are evenly distributed and have a moderate density, ensuring sufficient modified points to significantly reduce the overall elongation of the base film 1, while also ensuring the continuity of the unmodified areas (non-pinhole corresponding positions), allowing most areas of the base film 1 to retain its original mechanical strength.

[0040] When the porosity P of the loose aluminum seed layer 2 is less than 15%, the areal density of the pinhole structure 21 is too low, and the number of discrete points that can be penetrated and acted on by ultraviolet light is insufficient, resulting in a limited modified area ratio (i.e., the total area of ​​discrete point-like damage regions formed on the base film 1 is a small proportion of the surface area of ​​the base film 1). At this time, although the discrete point-like damage regions corresponding to each pinhole structure 21 can undergo molecular chain breakage or cross-linking, due to the large spacing and sparse distribution of the discrete point-like damage regions, the points effectively pinned in the molecular chain network are insufficient to form a significant constraint on the overall elongation, which macroscopically manifests as an elongation decrease of less than 5%. Under these circumstances, the composite aluminum current collector will still undergo irreversible elongation deformation in the subsequent coating and baking process, and problems such as electrode size deviation and coating peeling cannot be effectively solved. The scheme with a porosity P of less than 15% has no practical application value.

[0041] When the porosity P of the loose aluminum seed layer 2 exceeds 40%, the areal density of the pinhole structure 21 is too high. This results in an excessive number of discrete point-like damage areas formed after ultraviolet light penetrates the pinholes, significantly reducing the spacing between adjacent damage areas and even causing them to overlap. Consequently, the modified area on the base film 1 becomes excessively high (significantly exceeding 40%). At this point, the polymer molecular chains in most areas of the base film 1 are broken or cross-linked, leaving very little of the original strength region unmodified. The tensile strength retention rate of the base film 1 drops below 80%. Under these conditions, the composite aluminum current collector is highly susceptible to tape breakage during high-speed winding and coating, failing to meet the basic strength requirements of the base film 1 for large-scale continuous production. The scheme with a porosity P exceeding 40% loses its processing reliability.

[0042] Furthermore, when the ratio of the thickness of the loose aluminum seed layer 2 to the aperture of the pinhole structure 21, H1 / D, is less than 0.5:1, the masking effect is insufficient, easily leading to near-whole-area light leakage and loss of the advantage of targeted damage. When H1 / D is greater than 2:1, light reflection and attenuation within the pinhole are severe, resulting in insufficient modification energy on the surface of the base film 1 and a significant decrease in modification efficiency. Therefore, this invention uses 0.5:1 ≤ H1 / D ≤ 2:1 to ensure that ultraviolet light can be effectively confined and transmitted within the pinhole channel while reaching the surface of the base film 1 with sufficient light intensity, thus achieving the optimal balance between targeted damage and sufficient modification. H1 / D determines the confinement capability and light energy transmission efficiency of the pinhole structure 21 for ultraviolet light. When H1 / D is in the range of 0.5:1 to 2:1, the pinhole can act as an effective natural micromask to confine ultraviolet light to the corresponding pinhole position, while also ensuring controllable attenuation of light during transmission within the pinhole channel, allowing the surface of the base film 1 to obtain sufficient modification energy.

[0043] More specifically, when H1 / D < 0.5:1, the channels of the pinhole structure 21 are too shallow or the aperture is too large, resulting in insufficient confinement of ultraviolet light. Incident light passes through the pinhole almost unobstructed, and the area of ​​the light spot formed on the surface of the base film 1 is much larger than the physical area of ​​the pinhole. The modified regions between adjacent pinhole structures 21 overlap, and the base film 1 is subjected to non-selective irradiation with near-complete light leakage. Under these conditions, the advantages of discrete point-like damage areas are completely lost. The polymer molecular chains throughout the base film 1 undergo varying degrees of breakage or cross-linking, leading to a significant decrease in tensile strength (retention rate < 70%). This negates the core value of targeted modification, making the composite aluminum current collector prone to strip breakage during high-speed winding, failing to meet the requirements of continuous production. When H1 / D > 2:1, the channels of the pinhole structure 21 are too deep or the aperture is too small, resulting in excessive reflections of ultraviolet light on the inner wall of the pinhole. Each reflection causes partial attenuation of light energy, and the light intensity reaching the surface of the base film 1 is reduced to below the critical value that is insufficient to break the polymer molecular chains (the C-C bond energy of PET is 3.6 eV, and the CO bond energy is 3.7 eV, corresponding to an ultraviolet photon energy ≥ 3.6 eV). At this point, the polymer molecular chains on the surface of the base film 1 are not sufficiently broken or cross-linked, the pinning effect of the discrete point-like damage areas on the molecular chain network is weak, the macroscopic elongation decrease is < 5%, and the coating and baking deformation problem cannot be effectively solved. Therefore, 0.5:1 ≤ H1 / D ≤ 2:1. In some other embodiments, H1 / D can also be 1:1 or 1.5:1.

[0044] Furthermore, the thickness of the dense aluminum functional layer 3 is H2. Since the depth of the pinhole structure 21 of the loose aluminum seed layer 2 is 10~500nm (i.e., the value of H1), when H2 is less than 50 nm, it cannot completely cover the pinhole structure 21 of the loose aluminum seed layer 2 (the thickness of the dense layer needs to be greater than the thickness of the loose aluminum seed layer 2 to completely seal the pores); when H2 is greater than 200 nm, it increases material cost and has limited performance improvement. At the same time, an excessively thick dense aluminum functional layer 3 will reduce the flexibility of the composite current collector. Therefore, in this invention, 50nm ≤ H2 ≤ 200nm. This ensures that the pinhole structure 21 is completely filled and covered, forming a continuous, defect-free dense conductive layer. Thus, without sacrificing conductivity and corrosion resistance, the adverse effects of an excessively thick aluminum layer on the flexibility and material cost of the composite current collector are avoided.

[0045] Specifically, the loose aluminum seed layer 2 has pinhole structures 21 penetrating along its thickness direction, with a thickness H1 of 10 nm to 500 nm. The pinhole structures 21 extend from the surface of the base film 1 to the upper surface of the loose aluminum seed layer 2. Since the pinhole depth of the loose aluminum seed layer 2 can reach 10 nm to 500 nm, when the thickness H2 of the dense aluminum functional layer 3 is less than 50 nm, the insufficiently thick dense aluminum functional layer 3 can only cover the surface protrusions of the loose aluminum seed layer 2 and cannot fill downwards to the bottom of the pinhole structures 21. At this time, the micropores remaining in the pinhole structures 21 will lead to two serious consequences. First, the conductive path is interrupted at the pinhole location, which increases the surface resistance of the composite aluminum current collector, reduces the current collection efficiency, and affects the rate performance and cycle life of the battery. Second, LiPF6 and trace amounts of HF in the electrolyte can penetrate into the interface between the base film 1 and the aluminum layer through the unsealed pinhole, corroding the bonding interface between the aluminum layer and the base film 1, leading to aluminum layer peeling, increased current collector resistance, and even failure, which seriously affects the long-term safety and reliability of the battery.

[0046] When the thickness H2 of the dense aluminum functional layer 3 exceeds 200 nm, although it ensures that the pinhole structure 21 is completely sealed, the excessively thick aluminum layer brings new problems. On the one hand, aluminum is a high-density metal (density 2.7 g / cm³). 3 An excessively thick aluminum layer significantly increases the overall mass of the composite current collector, weakening its lightweight advantage over traditional pure aluminum foil and thus reducing the battery's mass energy density. Furthermore, increased aluminum layer thickness leads to increased overall bending stiffness and decreased flexibility, making the aluminum layer prone to cracking or even breakage during battery winding, affecting product yield. In addition, an excessively thick aluminum layer also means higher material consumption and longer evaporation time, increasing manufacturing costs and reducing production efficiency.

[0047] The base film 1 is made of one or more of polyethylene terephthalate (PET), polyimide (PP), polypropylene (PP), and polybutylene terephthalate (PP). PET has superior overall performance, low cost, good adhesion to the aluminum layer, and is sensitive to CO bonds and decarbonylation reactions in its molecular chain under UV irradiation, resulting in high modification efficiency. PI (polyimide) has excellent heat resistance (long-term operating temperature >300℃), but high cost; its mechanical properties decrease relatively less under UV irradiation, and its modification efficiency is slightly lower than PET. PP (polypropylene) has low cost, but very low polarity and poor adhesion to the aluminum layer, requiring strong plasma pretreatment before UV treatment. PBT (polybutylene terephthalate) has good processability, but its heat resistance is slightly inferior to PET.

[0048] The thickness of the base film 1 is H3. When H3 is less than 4 μm, the mechanical strength of the base film 1 is insufficient, making it difficult to withstand the belt tension during the evaporation and coating processes. When H3 is greater than 12 μm, the energy density advantage of the composite current collector weakens, and an excessively thick base film 1 reduces the modification efficiency of the surface layer by ultraviolet light (the light penetration depth is limited, and an excessively thick base film 1 has a large proportion of unmodified parts, diluting the elongation control effect). Therefore, in this invention, 4 μm ≤ H3 ≤ 12 μm. This ensures that the base film 1 has sufficient mechanical strength to withstand the belt tension during the evaporation and coating processes, while maintaining the energy density advantage of the composite current collector and ensuring the modification efficiency of the surface layer of the base film 1 by ultraviolet light, thereby achieving optimal performance in terms of processing feasibility, energy density, and elongation. Achieving an optimal balance between elongation control and performance is crucial. Specifically, the thickness of the base film 1, serving as the support and mechanical bearing layer of the composite current collector, directly determines the tensile strength of the composite current collector during high-speed winding evaporation, electrode coating, and rolling processes. Simultaneously, the thickness of the base film 1 significantly affects the overall quality of the composite current collector (and consequently the battery's mass energy density) and the efficiency of ultraviolet light modification of the base film 1's surface (and thus the range of elongation control). When H3 is within the range of 4μm to 12μm, the base film 1 possesses sufficient tensile strength, a low volumetric mass ratio, and suitable ultraviolet light penetration modification efficiency, comprehensively meeting the mechanical, energy density, and process compatibility requirements of the composite current collector for the base film 1.

[0049] The loose aluminum seed layer 2 has a gradient porosity structure along its thickness direction. The loose aluminum seed layer 2 includes a bottom layer near the base film 1 and an upper layer connected to the bottom layer. The porosity of the bottom layer is greater than that of the upper layer, and the pore size of the pinhole structures 21 located in the bottom layer is larger than that of the pinhole structures 21 located in the upper layer. The thickness of the upper layer accounts for 60%-70% of the thickness of the loose aluminum seed layer 2. The pore size of the pinhole structures 21 located in the bottom layer is D1, and the pore size of the pinhole structures 21 located in the upper layer is D2, where 0.8μm≤D1≤6μm and 0.3μm≤D2≤2μm. This forms a gradient optical path structure that allows for "large apertures guiding light in the bottom layer and small apertures converging in the upper layer."

[0050] Furthermore, when ultraviolet light is incident from the base film 1, the large-aperture pinholes (0.8μm~6μm) on the bottom layer provide a high-flux light-guiding entrance, allowing more ultraviolet light to effectively couple into the loose aluminum seed layer 2. Subsequently, the light enters the small-aperture pinhole structure 21 (0.3μm~2μm) on the upper layer. Due to the lower porosity and gradually narrowing pore size of the upper layer, the light is gradually gathered and focused during transmission, ultimately reaching the surface of the base film 1 with a higher energy density. Thus, the large-aperture high-flux channel on the bottom layer and the small-aperture convergence structure on the upper layer work together to form a "light-concentrating-light-guiding" effect, significantly improving the overall light utilization efficiency of ultraviolet light from incident to reaching the surface of the base film 1.

[0051] This invention also provides a method for preparing a composite aluminum current collector, such as... Figure 3 As shown, the preparation method of the composite aluminum current collector includes steps S2100 to S2400.

[0052] It should be noted that the preparation method of the composite aluminum current collector provided by the present invention may include the embodiments of the above-described composite aluminum current collector, and the beneficial effects of the above-described composite aluminum current collector can be applied to the preparation method of the composite aluminum current collector. Similarly, the embodiments of the above-described composite aluminum current collector may include embodiments of the preparation method of the composite aluminum current collector, and the beneficial effects of the preparation method of the composite aluminum current collector can be applied to the above-described composite aluminum current collector.

[0053] Step S2100 provides a base film 1. The material of the base film 1 may be, but is not limited to, one or more of polyethylene terephthalate (PET), polyimide, polypropylene, and polybutylene terephthalate (PET). PET has superior overall performance, low cost, good adhesion to the aluminum layer, and is sensitive to CO bonds and decarbonylation reactions in the PET molecular chain under UV irradiation, resulting in high modification efficiency. PI (polyimide) has excellent heat resistance (long-term operating temperature >300℃), but high cost; its mechanical properties decrease relatively little under UV irradiation, and its modification efficiency is slightly lower than PET. PP (polypropylene) has low cost, but very low polarity and poor adhesion to the aluminum layer, requiring strong plasma pretreatment before UV treatment. PBT (polybutylene terephthalate) has good processability, but its heat resistance is slightly inferior to PET.

[0054] In other embodiments, pretreatment of the base film 1 is also included. For example, plasma cleaning or corona discharge treatment is performed on the aluminum-to-be-plated surface of the base film 1 to improve surface activity and adhesion.

[0055] The thickness of the base film 1 is H3. When H3 is less than 4 μm, the mechanical strength of the base film 1 is insufficient, making it difficult to withstand the belt tension during the evaporation and coating processes. When H3 is greater than 12 μm, the energy density advantage of the composite current collector weakens, and an excessively thick base film 1 reduces the modification efficiency of ultraviolet light on the surface (the light penetration depth is limited, and an excessively thick base film 1 has a large proportion of unmodified parts, diluting the elongation control effect). Therefore, in this invention, 4 μm ≤ H3 ≤ 12 μm. This ensures that the base film 1 has sufficient mechanical strength to withstand the belt tension during the evaporation and coating processes, while maintaining the energy density advantage of the composite current collector and ensuring the modification efficiency of ultraviolet light on the surface of the base film 1, thus achieving the best balance between processing feasibility, energy density, and elongation control effect. Specifically, the base film 1 serves as a composite current collector... The thickness of the fluid support layer and the mechanical bearing layer directly determines the tensile strength of the composite current collector during high-speed winding evaporation, electrode coating, and rolling processes. Simultaneously, the thickness of the base film 1 significantly affects the overall quality of the composite current collector (and consequently the energy density of the battery) and the efficiency of ultraviolet light modification of the base film 1 surface (and consequently the range of elongation control). When H3 is within the range of 4μm to 12μm, the base film 1 possesses sufficient tensile strength, a low volumetric mass ratio, and suitable ultraviolet light penetration modification efficiency, fully meeting the mechanical, energy density, and process adaptability requirements of the composite current collector for the base film 1.

[0056] In step S2200, a loose aluminum seed layer 2 is formed on at least one side surface of the base film 1. The loose aluminum seed layer 2 has a plurality of pinhole structures 21 penetrating along the thickness direction. The porosity of the loose aluminum seed layer 2 is P, 15%≤P≤40%.

[0057] In some embodiments, the aperture of the pinhole structure 21 is D, and the thickness of the loose aluminum seed layer 2 is H1, where 0.5μm≤D≤5μm and 10nm≤H1≤500nm. When the diameter of the pinhole structure 21 is less than 0.5μm, the ultraviolet diffraction effect is limited (wavelength to aperture ratio <1), resulting in extremely low optical coupling efficiency; when it is greater than 5μm, the masking effect is insufficient, and the single-pore modification area is too large, approaching the effect of full-surface irradiation. Therefore, by controlling the aperture D of the pinhole structure 21 within the range of 0.5μm≤D≤5μm, the present invention achieves an optimal balance between ultraviolet diffraction efficiency and mask confinement effect, thereby maximizing the retention of the strength of the base film 1 while effectively reducing the elongation of the composite aluminum current collector. In other embodiments, D can also be 1μm, 2μm, or 3μm.

[0058] When the porosity of the loose aluminum seed layer 2 is below 15%, the modified area is insufficient, resulting in limited reduction in elongation. When it is above 40%, the modified area of ​​the base film 1 is too large, causing the strength retention rate to drop below 80%. Therefore, in this invention, by controlling the porosity P of the loose aluminum seed layer 2 within the range of 15% ≤ P ≤ 40%, the optimal balance between the modified area of ​​the base film 1 by ultraviolet light and the strength retention rate of the base film 1 can be ensured. This effectively reduces the elongation of the composite aluminum current collector while ensuring that the base film 1 has sufficient processing strength. Specifically, the porosity P determines the areal density of the pinhole structure 21 in the loose aluminum seed layer 2, i.e., the number of discrete points that ultraviolet light can penetrate and act on the base film 1. When 15% ≤ P ≤ 40%, the pinholes are evenly distributed and have a moderate density, ensuring sufficient modified points to significantly reduce the overall elongation of the base film 1, while also ensuring the continuity of the unmodified areas (non-pinhole corresponding positions), allowing most areas of the base film 1 to retain its original mechanical strength.

[0059] When the thickness of the loose aluminum seed layer 2 is less than 10 nm, the aluminum layer is discontinuous, resulting in insufficient pinhole masking effect; when it is greater than 500 nm, the aspect ratio H1 / D is too large (>2:1), causing severe attenuation of ultraviolet light reflection on the inner wall of the pinhole, leading to insufficient modification energy on the surface of the base film 1. Therefore, in this invention, by controlling the thickness H1 of the loose aluminum seed layer 2 within the range of 10 nm ≤ H1 ≤ 500 nm, the integrity and functionality of the pinhole structure 21 as a natural micromask for ultraviolet light can be ensured, while also ensuring that ultraviolet light can effectively penetrate the pinhole to reach the surface of the base film 1 for sufficient modification. In addition, the thickness H1 of the loose aluminum seed layer 2 determines the aspect ratio (H1 / D) of the pinhole structure 21, which directly affects the transmission efficiency of ultraviolet light in the pinhole channel. When H1 is controlled within the range of 10 nm to 500 nm, combined with an aperture D of 0.5 μm to 5 μm, the aspect ratio of the pinhole can be maintained within a reasonable range of 0.5:1 to 2:1. Within this aspect ratio range, the number of reflections of ultraviolet light on the inner wall of the pinhole is moderate, and the light intensity attenuation is controllable, enabling effective transmission to the surface of the base film 1 and providing sufficient modification energy. In other embodiments, H1 can also be 50nm, 100nm, 200nm, or 300nm.

[0060] In a specific implementation, under a vacuum environment with a first preset vacuum level, a loose aluminum seed layer 2 is formed on at least one side surface of the base film 1 by evaporation at a first preset evaporation rate, so that the loose aluminum seed layer 2 forms the pinhole structure 21. The first preset evaporation rate is v1, 8nm / s≤v1≤15nm / s.

[0061] When v1 is below 8 nm / s, aluminum atoms have sufficient time to diffuse and migrate, forming a dense structure, making it difficult for pinhole porosity to reach more than 15%. When v1 is above 15 nm / s, the aluminum layer is too loose, and the porosity of the aluminum layer exceeds 40%, the pinhole size is too large and the distribution is out of control, making it difficult for subsequent dense layers to completely seal the pores.

[0062] In this invention, by controlling the first preset evaporation rate v1 to 8nm / s≤v1≤15nm / s when forming the loose aluminum seed layer 2, aluminum atoms are stacked on the surface of the base film 1 at a moderate deposition rate. This avoids the formation of a dense structure due to excessive atomic diffusion time, and also avoids porosity runaway due to excessive deposition rate. Thus, the optimal balance is achieved between the porosity, pinhole size and distribution uniformity of the loose layer.

[0063] Specifically, during the vacuum evaporation process, aluminum atoms are deposited in gaseous form onto the surface of the base film 1 and then diffuse and migrate on the surface. The migration distance is negatively correlated with the deposition rate. When the deposition rate is low, aluminum atoms have sufficient time to diffuse and migrate on the surface of the base film 1, tending to fill the gaps between existing atoms and forming a dense thin film structure with regular atomic arrangement and extremely low porosity. When the deposition rate is moderate, aluminum atoms are covered by subsequently arriving aluminum atoms before they have fully diffused to fill all the gaps, thus retaining micron-sized pinhole defects inside and on the surface of the film, forming a loose structure. When the deposition rate is too high, aluminum atoms are covered by subsequent atoms almost before they have time to diffuse on the surface of the base film 1, forming a columnar loose structure with disordered atomic arrangement and extremely high porosity, and the size and distribution of pinholes are severely out of control.

[0064] When the first preset evaporation rate v1 is less than 8 nm / s, the surface diffusion and migration time of aluminum atoms is sufficient. Each aluminum atom has enough time to find the lowest energy lattice position at the deposition site, and the interatomic gaps are effectively filled, resulting in a denser film. At this time, the porosity of the formed aluminum layer is difficult to reach more than 15%, and the number of pinhole structures 21 is sparse or even unable to form through-hole channels that penetrate the entire thickness of the loose layer. Under these circumstances, ultraviolet light cannot effectively penetrate the aluminum layer to reach the surface of the base film 1, discrete point damage areas cannot be formed, and the elongation control effect is negligible (decreased by <5%). It cannot solve the coating and baking deformation problem, so the scheme with v1 < 8 nm / s is not practical. When the first preset evaporation rate v1 is greater than 15 nm / s, the diffusion and migration time of aluminum atoms on the surface of the base film 1 is severely insufficient, and the deposition rate is much higher than the limit rate at which atoms can complete ordered stacking. Aluminum atoms are randomly stacked on the surface of the base film 1 in an almost "stacking" manner, forming an extremely loose structure with a large number of micropores and macropores. Therefore, the optimal performance is achieved when 8 nm / s ≤ v1 ≤ 15 nm / s. In some other implementations, v1 can also be 10 nm / s or 12 nm / s.

[0065] The first preset vacuum level is B, 1×10⁻⁶. -2 Pa≤B≤5×10 -2 Pa. This maintains a suitable residual gas atmosphere in the vapor deposition chamber, utilizing the influence of residual gas molecules on the deposition behavior of aluminum atoms to assist in the formation of a uniform and controllable pinhole structure 21, while ensuring that aluminum atoms have sufficient kinetic energy to complete film growth, thereby achieving the best balance between the uniformity and controllability of the pinhole structure 21 and the stability of the vapor deposition process.

[0066] Specifically, during vacuum evaporation, the concentration and mean free path of residual gas molecules (mainly water vapor, oxygen, nitrogen, etc.) are directly affected by the vacuum level. When 1×10 -2 Pa≤B≤5×10 -2 At a vacuum level of Pa, the concentration of residual gas molecules in the chamber is moderate. During the process of aluminum atoms flying from the evaporation source to the surface of the base film 1, a small number of collisions occur with the residual gas molecules, and the flight direction and kinetic energy of the aluminum atoms are moderately disturbed. At the same time, the residual gas molecules may be captured by the grown aluminum layer on the surface of the base film 1, forming nanoscale bubbles or voids, which further promotes the formation of pinhole structures 21. Therefore, when this vacuum level range is matched with a deposition rate of 8 nm / s to 15 nm / s, pinhole structures 21 with a porosity of 15% to 40%, a pore size of 0.5 μm to 5 μm, uniform distribution, and penetrating the thickness direction can be formed.

[0067] When the first preset vacuum level B is higher than 5×10 -2 Pa (meaning insufficient vacuum, excessive residual gas in the chamber, absolute pressure higher than 5 × 10⁻⁶) -2 When the residual gas concentration is too high (e.g., 1 Pa), aluminum atoms collide frequently with these molecules during their flight path, significantly shortening the mean free path. This results in insufficient kinetic energy for aluminum atoms reaching the surface of the base film 1, preventing the formation of a dense film structure. Simultaneously, a large number of residual gas molecules are trapped within the grown aluminum layer, leading to excessive and uncontrollable bubbles or pinhole defects. This results in an extremely porous and non-uniform film structure, with porosity deviations exceeding ±20% in different regions. Furthermore, excessive residual gas concentration may introduce oxygen contamination, causing aluminum oxide formation on the aluminum surface and reducing the bonding strength between the aluminum layer and subsequent dense layers. When the first preset vacuum level B is below 1 × 10⁻⁶, the situation worsens. -2 Pa (i.e., vacuum is too high, absolute pressure is less than 1×10⁻⁶) -2 At a pressure of 100 Pa, the residual gas molecules in the chamber are extremely scarce, and aluminum atoms hardly collide during their flight, depositing onto the surface of the base film 1 in a high-energy and high-purity state. At this point, the surface diffusion and migration ability of aluminum atoms is enhanced, the film layer tends to be denser, and the effect of residual gas in assisting the formation of pinholes is greatly reduced. Even with a deposition rate of 8 nm / s to 15 nm / s, the number of pinhole structures 21 formed is still relatively small (porosity is difficult to reach 15%).

[0068] Therefore, the present invention 1×10 -2 Pa≤B≤5×10 -2 Pa ensures, on the one hand, that the concentration of residual gas molecules in the chamber is moderate, which can help the loose aluminum seed layer 2 form a uniform and controllable pinhole structure 21, and together with the deposition rate of 8nm / s~15nm / s, achieve a porosity of 15%~40% and a pore size of 0.5μm~5μm; on the other hand, it avoids problems such as uncontrolled pinhole structure 21, aluminum layer oxidation and decreased film adhesion caused by excessive residual gas, while ensuring the economy of the vapor deposition process.

[0069] When the ratio of the thickness of the loose aluminum seed layer 2 to the aperture of the pinhole structure 21, H1 / D, is less than 0.5:1, the masking effect is insufficient, leading to near-whole-area light leakage and loss of the advantage of targeted damage. When H1 / D is greater than 2:1, light reflection and attenuation within the pinhole are severe, resulting in insufficient modification energy for the surface of the base film 1 and a significant decrease in modification efficiency. Therefore, this invention uses a ratio of 0.5:1 ≤ H1 / D ≤ 2:1 to ensure that ultraviolet light can be effectively confined and transmitted within the pinhole channel while reaching the surface of the base film 1 with sufficient intensity, thus achieving the optimal balance between targeted damage and sufficient modification. H1 / D determines the confinement capability and light energy transmission efficiency of the pinhole structure 21 for ultraviolet light. When H1 / D is in the range of 0.5:1 to 2:1, the pinhole can act as an effective natural micromask to confine ultraviolet light to the corresponding pinhole position, while also ensuring controllable attenuation of light during transmission within the pinhole channel, allowing the surface of the base film 1 to obtain sufficient modification energy.

[0070] More specifically, when H1 / D < 0.5:1, the channels of the pinhole structure 21 are too shallow or the aperture is too large, resulting in insufficient confinement of ultraviolet light. Incident light passes through the pinhole almost unobstructed, and the area of ​​the light spot formed on the surface of the base film 1 is much larger than the physical area of ​​the pinhole. The modified regions between adjacent pinhole structures 21 overlap, and the base film 1 is subjected to non-selective irradiation with near-complete light leakage. Under these conditions, the advantages of discrete point-like damage areas are completely lost. The polymer molecular chains throughout the base film 1 undergo varying degrees of breakage or cross-linking, leading to a significant decrease in tensile strength (retention rate < 70%). This negates the core value of targeted modification, making the composite aluminum current collector prone to strip breakage during high-speed winding, failing to meet the requirements of continuous production. When H1 / D > 2:1, the channels of the pinhole structure 21 are too deep or the aperture is too small, resulting in excessive reflections of ultraviolet light on the inner wall of the pinhole. Each reflection causes partial attenuation of light energy, and the light intensity reaching the surface of the base film 1 is reduced to below the critical value that is insufficient to break the polymer molecular chains (the C-C bond energy of PET is 3.6 eV, and the CO bond energy is 3.7 eV, corresponding to an ultraviolet photon energy ≥ 3.6 eV). At this point, the polymer molecular chains on the surface of the base film 1 are not sufficiently broken or cross-linked, the pinning effect of the discrete point-like damage areas on the molecular chain network is weak, the macroscopic elongation decrease is < 5%, and the coating and baking deformation problem cannot be effectively solved. Therefore, 0.5:1 ≤ H1 / D ≤ 2:1. In some other embodiments, H1 / D can also be 1:1 or 1.5:1.

[0071] The loose aluminum seed layer 2 has a gradient porosity structure along its thickness direction. The loose aluminum seed layer 2 includes a bottom layer near the base film 1 and an upper layer connected to the bottom layer. The porosity of the bottom layer is greater than that of the upper layer, and the pore size of the pinhole structures 21 located in the bottom layer is larger than that of the pinhole structures 21 located in the upper layer. The thickness of the upper layer accounts for 60%-70% of the thickness of the loose aluminum seed layer 2. The pore size of the pinhole structures 21 located in the bottom layer is D1, and the pore size of the pinhole structures 21 located in the upper layer is D2, where 0.8μm≤D1≤6μm and 0.3μm≤D2≤2μm. This forms a gradient optical path structure that allows for "large apertures guiding light in the bottom layer and small apertures converging in the upper layer."

[0072] Furthermore, when ultraviolet light is incident from the base film 1, the large-aperture pinholes (0.8μm~6μm) on the bottom layer provide a high-flux light-guiding entrance, allowing more ultraviolet light to effectively couple into the loose aluminum seed layer 2. Subsequently, the light enters the small-aperture pinhole structure 21 (0.3μm~2μm) on the upper layer. Due to the lower porosity and gradually narrowing pore size of the upper layer, the light is gradually gathered and focused during transmission, ultimately reaching the surface of the base film 1 with a higher energy density. Thus, the large-aperture high-flux channel on the bottom layer and the small-aperture convergence structure on the upper layer work together to form a "light-concentrating-light-guiding" effect, significantly improving the overall light utilization efficiency of ultraviolet light from incident to reaching the surface of the base film 1.

[0073] In some other implementations, step S2200 is followed by step S2210.

[0074] Step S2210 involves online introduction of low-pressure argon plasma to roughen the surface of the loose aluminum seed layer 2, forming a micro-nano-scale rough structure on its surface. The plasma treatment power is 50-200W, and the treatment time is 5-20s. This reduces the specular reflectivity of ultraviolet light and increases the proportion of incident light coupling into the pinholes. Without damaging the pinhole structure 21 of the loose aluminum seed layer 2, this effectively reduces the specular reflectivity of the aluminum layer surface to ultraviolet light and increases the proportion of incident light coupling into the pinholes, thus achieving a more complete modification effect on the base film 1 under the same ultraviolet irradiation dose.

[0075] Specifically, on the surface of the porous aluminum seed layer 2 prepared by vacuum evaporation, aluminum atoms are typically stacked with relatively flat crystal orientations, forming a smooth surface with certain specular reflection characteristics. When ultraviolet light is incident on this smooth surface at a certain angle, most of the light energy is lost due to specular reflection following the geometric optical reflection law (the specular reflectivity can reach 60%~80%), and only a small portion of the light can couple into the interior of the porous layer through the pinhole entrance. This specular reflection loss significantly reduces the effective light energy reaching the surface of the base film 1, resulting in low ultraviolet light utilization efficiency.

[0076] In this invention, after depositing a loose aluminum seed layer 2 and before ultraviolet irradiation, a low-pressure argon plasma is introduced online to bombard the aluminum layer surface. High-energy argon ions in the argon plasma bombard the aluminum layer surface under an electric field acceleration, forming a micro-nano-scale uneven structure (roughness Ra can reach 50nm~200nm) on the aluminum layer surface through physical sputtering. This micro-nano-scale rough structure transforms the aluminum layer surface from a smooth mirror surface to a diffuse reflective surface. When ultraviolet light is incident on this rough surface, the light undergoes multiple scattering at the micro-nano uneven structure, significantly reducing the specular reflection component. More light is scattered and changes direction, with some light being guided to the vicinity of the pinhole entrance during multiple scattering, and then coupled into the pinhole channel. Through surface roughening treatment, the coupling efficiency of ultraviolet light at the pinhole entrance can be increased by 20%~40%, significantly increasing the effective light energy reaching the surface of the base film 1. The degree of modification of the base film 1 surface is significantly enhanced under the same irradiation dose.

[0077] Meanwhile, argon plasma is an inert gas plasma that only roughens the aluminum layer surface through physical bombardment without undergoing chemical reactions. It does not alter the chemical composition of the aluminum layer or generate an oxide layer on its surface. Therefore, the chemical composition of the roughened loose aluminum seed layer 2 remains unchanged, and it does not affect the subsequent deposition and growth of the dense aluminum functional layer 3 or the interfacial bonding strength.

[0078] When the argon plasma treatment power is below 50W, the kinetic energy of the argon ions is insufficient, resulting in weak physical bombardment of the aluminum layer surface. This makes it impossible to form an effective micro / nano-level roughened structure in a short time, and the aluminum layer surface retains a high specular reflectivity. The light coupling improvement effect is not significant (<5%), and the improvement in ultraviolet light utilization efficiency is extremely limited, failing to make a substantial contribution to this invention. When the argon plasma treatment power is above 200W, the argon ion bombardment energy is too high, not only roughening the aluminum layer surface but also damaging the pinhole structure 21 of the loose aluminum seed layer 2. High-energy argon ions may cause aluminum atoms at the pinhole edges to migrate, melt, or re-sputter, leading to increased pinhole diameter, blunted edges, or even collapse of the pinhole structure 21. This destroys the function of the pinhole as a natural micromask, reduces the confined transmission capability of ultraviolet light, and decreases the control precision of the modified area.

[0079] When the argon plasma treatment time is less than 5 seconds, even with a power setting within the range of 50W to 200W, the insufficient bombardment time leads to inadequate roughening, limited improvement in the surface roughness of the aluminum layer, and an inability to adequately reduce specular reflectivity. The improvement in optical coupling efficiency is also minimal (<5%), and its synergistic effect on subsequent UV modification is negligible. When the argon plasma treatment time exceeds 20 seconds, the excessive bombardment time results in over-roughening of the aluminum layer surface, or even complete sputtering removal of some aluminum layers. This reduces the thickness of the loose aluminum seed layer 2 and damages the pinhole structure 21, affecting the precision of subsequent UV irradiation modification and the integrity of the dense layer sealing. Furthermore, the excessively long treatment time reduces production line efficiency, contradicting the requirements of large-scale mass production.

[0080] This invention controls the low-pressure argon plasma treatment power to 50W~200W and the treatment time to 5s~20s. On the one hand, it ensures the formation of a sufficiently rough micro-nano structure on the surface of the loose aluminum seed layer 2, effectively reducing the specular reflectivity of ultraviolet light (the specular reflectivity can be reduced from 60%~80% to 20%~40%), and significantly increasing the proportion of incident light coupled into the pinholes (the light coupling efficiency is increased by 20%~40%). This results in a more complete modification effect on the base film 1 under the same ultraviolet irradiation dose. On the other hand, it avoids damage to the pinhole structure 21 caused by excessively high power or excessively long treatment time, ensuring that the size, morphology and distribution of the pinholes remain within a controllable range, and guaranteeing the effectiveness of subsequent ultraviolet spot irradiation and dense layer sealing.

[0081] In step S2300, ultraviolet light is used to irradiate the base film 1 on which the loose aluminum seed layer 2 is provided. The ultraviolet light passes through the pinhole structure 21 and irradiates the surface of the base film 1, causing discrete point-like damage areas to be formed on the surface of the base film 1 at the positions corresponding to the pinhole structure 21. The polymer molecular chains in the discrete point-like damage areas are damaged (e.g., broken or cross-linked).

[0082] In practice, the semi-finished product coated with the loose aluminum seed layer 2 is fed into the ultraviolet irradiation chamber between the two-stage evaporation stations. Under air or an inert atmosphere, the side of the base film 1 coated with the loose aluminum seed layer 2 is irradiated with ultraviolet light with a wavelength of 200nm~380nm. The irradiation dose is controlled at 50mJ / cm. 2 ~500mJ / cm 2 Wherein, the wavelength of the ultraviolet light is L, the irradiation dose is S, 200nm≤L≤380nm, and 50mJ / cm². 2 ≤S≤500mJ / cm 2 .

[0083] Ultraviolet light can pass through the pinholes of the loose aluminum seed layer 2 and directly irradiate the surface of the underlying base film 1, forming discrete point-like damage areas on the base film 1 that correspond one-to-one with the pinhole locations. The polymer molecular chains in the point-damaged areas break or crosslink, which can effectively reduce the overall elongation of the base film 1. Meanwhile, the areas of the base film 1 not covered by pinholes are not irradiated by ultraviolet light and retain their original mechanical strength.

[0084] Specifically, the pinhole structures 21 embedded in the loose aluminum seed layer 2 act as natural micromasks for ultraviolet light, selectively allowing incident ultraviolet light to pass through. Ultraviolet light can only pass through the loose aluminum seed layer 2 through the pinholes to reach the surface of the base film 1, while the regions of the loose aluminum seed layer 2 between the pinhole structures 21 block and shield the ultraviolet light. Since the pinholes are uniformly distributed in the loose aluminum seed layer 2 and have a diameter of 0.5 μm to 5 μm, ultraviolet light undergoes diffraction when passing through the pinholes, forming a modified light spot (diffraction diameter expansion coefficient η) on the surface of the base film 1 that is slightly larger than the physical area of ​​the pinholes. diff (≈1.05~1.5), so that the actual coverage area of ​​the discrete point damage area is slightly larger than the sum of the cross-sectional areas of the pinholes, ensuring that the pinning effect of the modified sites on the molecular chain network is fully effective.

[0085] When the wavelength L of ultraviolet light is below 200 nm, although the photon energy in the vacuum ultraviolet band is high (>6.2 eV), this wavelength of ultraviolet light is strongly absorbed by oxygen when propagating in the air, generating a large amount of ozone. This requires an expensive vacuum ultraviolet light source and a high-purity nitrogen purging system, which drastically increases equipment costs. At the same time, the strong oxidizing properties of ozone will corrode equipment seals and chamber walls, accelerating equipment aging, and the treatment of exhaust gas with high concentrations of ozone also increases the environmental burden. In addition, ultraviolet light with wavelengths below 200 nm has a very shallow penetration depth (<0.1 μm) in the polymer base film 1, which can only modify the thinnest outermost layer of the base film 1, and has a very limited pinning effect on the overall elongation. The modification efficiency is seriously out of balance with the investment cost.

[0086] When the ultraviolet light wavelength L is higher than 380 nm, the photon energy is lower than 3.3 eV, which is less than the bond energies of the C-C bonds (3.6 eV) and CO bonds (3.7 eV) in the PET molecular chain. Therefore, it cannot effectively break the covalent bonds of the polymer molecular chain, and can only induce limited excited-state relaxation or a weak photothermal effect on the surface of the base film 1, which is insufficient to cause molecular chain breakage or cross-linking. At this time, an effective discrete point-like damage zone cannot be formed on the surface of the base film 1, the molecular chain network is not effectively pinned, and the macroscopic elongation decreases by less than 5%, failing to solve the coating and baking deformation problem.

[0087] This invention controls the ultraviolet light wavelength within the range of 200nm to 380nm, ensuring that the ultraviolet light possesses sufficient single-photon energy to break the covalent bonds (E) in the polymer molecular chain. photon ≥E bondIt also has the key optical parameter selection of appropriate penetration depth to achieve effective modified layer thickness (the modified layer thickness covers the molecular chain network of the base film 1 surface).

[0088] More specifically, the ultraviolet light includes ultraviolet light in the deep ultraviolet band and ultraviolet light in the near ultraviolet band, wherein the wavelength of the deep ultraviolet band is L1, the wavelength of the near ultraviolet band is L2, 200nm≤L≤280nm, and 315nm≤L≤380nm.

[0089] Deep ultraviolet (DUV) has high energy (4.4–6.2 eV) and can effectively break the CC and CO bonds in PET (bond energies of 3.6 eV and 3.7 eV, respectively), but its penetration depth is shallow (approximately 0.1–0.5 μm). Near ultraviolet (UV) has deeper penetration (approximately 0.5–2 μm) and is suitable for thicker base films or applications requiring a larger modification area. Below 200 nm, equipment costs increase dramatically and ozone generation is excessive; above 380 nm, photon energy is insufficient to effectively break polymer molecular chains.

[0090] The deep ultraviolet band (200nm~280nm) has a weak diffraction effect and high energy density, making it suitable for pinholes with an equivalent diameter of 0.5μm~2μm. The morphology of the damage points is accurate, and the impact on the strength of the base film is small. The near ultraviolet band (315~380 nm) has a strong diffraction effect and large penetration depth, making it suitable for pinholes with an equivalent diameter of 2~6μm. The single-pore modification area is large, and the overall modification efficiency is high.

[0091] The irradiation dose was controlled at 50 mJ / cm. 2 ~500mJ / cm 2 Below 50 mJ / cm 2 When the degree of modification is insufficient, the elongation decreases by less than 5%; when it exceeds 500 mJ / cm 2 The surface layer of the base film 1 is excessively degraded, with a strength retention rate of less than 70%, and the conveyor belt speed of the production line needs to be significantly reduced, affecting production efficiency.

[0092] Specifically, the irradiation dose S determines the degree of reaction in which the polymer molecular chains on the surface of the base film 1 break or crosslink. When S is at 50 mJ / cm 2 ~500mJ / cm 2 Within the specified range, the surface of the base film 1 receives sufficient ultraviolet light energy, causing the polymer molecular chains in the discrete point-like damage area to fully break or cross-link, forming a sufficient number of pinning points to effectively pin the molecular chain network. The macroscopic elongation rate is significantly reduced, while the degree of modification of the surface of the base film 1 is controlled within a reasonable range, without excessive degradation, and the tensile strength retention rate remains between 81.9% and 94.3%.

[0093] When the irradiation dose S is below 50 mJ / cm 2At this time, the ultraviolet light energy is insufficient to cause sufficient breakage or cross-linking of the polymer molecular chains on the surface of the base film 1. In this state, only limited excited-state relaxation or weak photochemical primary reactions occur within the discrete point-like damage areas, resulting in extremely low degrees of molecular chain breakage or cross-linking, insufficient to effectively pin the molecular chain network. Macroscopically, this manifests as a decrease in elongation of less than 5%, and the composite aluminum current collector still undergoes significant irreversible elongation deformation during subsequent coating and baking processes. Problems such as electrode dimensional deviations and coating peeling remain unresolved.

[0094] When the irradiation dose S is higher than 500 mJ / cm 2 Excessive ultraviolet light energy causes excessive degradation of the surface layer of base film 1. Within the discrete point-like damage area, the polymer molecular chains not only undergo moderate breakage and cross-linking, but also further undergo excessive chain breaking, oxidative degradation, and even carbonization reactions, leading to embrittlement and loss of strength of the material in the damage area. At the same time, excessively high doses may also indirectly affect some areas that were originally shielded by the aluminum layer (such as the weak points of the aluminum layer at the edge of the pinhole), exacerbating the loss of strength of base film 1.

[0095] This invention controls the irradiation dose S to 50 mJ / cm 2 ~500mJ / cm 2 Within the specified range, on the one hand, it ensures that the discrete point-like damage area receives sufficient ultraviolet light energy, so that the polymer molecular chains can be fully broken or cross-linked, forming an effective pinning of the molecular chain network, thereby achieving a significant reduction in elongation (14%~38%); on the other hand, it ensures that the degree of modification is limited to a reasonable range, the base film 1 does not undergo excessive degradation and embrittlement, and the tensile strength retention rate remains above 81.9%.

[0096] Furthermore, the degree of modification is positively correlated with porosity P and irradiation dose S, satisfying a quantitative relationship: modified area ratio ≈ porosity P × diffraction diameter expansion coefficient η diff Among them, the diffraction diameter expansion coefficient η diff ≈1+λ·z / D 2 (λ is the ultraviolet wavelength, z is the pinhole depth, i.e., the thickness of the porous layer H1, and D is the pinhole diameter), the theoretical value is 1.05~1.5. For the target elongation range, high porosity corresponds to low irradiation dose, and low porosity corresponds to high irradiation dose, so as to minimize the strength loss of the base film 1 while ensuring the modification effect.

[0097] Specifically, the actual modified area ratio of the discrete point-like damage regions on the base film 1 is not simply equal to the porosity P of the loose aluminum seed layer 2, but follows the quantitative relationship described above. Due to the diffraction effect of ultraviolet light passing through the micron-sized pinholes, the modified light spot area formed on the surface of the base film 1 is larger than the physical cross-sectional area of ​​the pinholes, and the degree of diameter expansion is determined by the diffraction diameter expansion coefficient η. diff Characterization. η diffThe diffraction effect is determined by the wavelength λ, the pinhole depth z (i.e., the thickness H1 of the loose layer), and the diameter D of the pinhole structure 21: the longer the wavelength, the deeper the pinhole, and the smaller the pore size, the more significant the diffraction effect. diff The larger the value (up to 1.5), the shorter the wavelength, the shallower the pinhole, and the larger the aperture, the higher the η value. diff The smaller the value (approaching 1.05), the more accurate the control of the modified area ratio becomes. This quantitative relationship provides a theoretical basis for the precise control of the modified area ratio.

[0098] This invention establishes a linkage control strategy between porosity P and irradiation dose S by setting the pinhole diameter D to 0.5μm≤D≤5μm and the porosity P to 15%≤P≤40%. This strategy enables the modified area ratio to be precisely controlled within the target range under the effect of diffraction diameter expansion, thereby minimizing the strength loss of the base film 1 while ensuring a significant reduction in elongation.

[0099] The ultraviolet light source is set at a preset tilt angle to the transport plane of the base film 1. Multiple sets of ultraviolet light sources are arranged alternately along the transport direction of the base film 1. The preset tilt angle is A, where 15° ≤ A ≤ 45°. The alternating arrangement of multiple light sources along the transport direction ensures irradiation uniformity. Oblique incidence reduces specular reflection loss on the top surface of the loose aluminum seed layer 2, increases the proportion of light coupling into the pinhole, and increases the number of reflections of light on the inner wall of the pinhole, enhancing the microcavity focusing effect and increasing the effective light intensity at the bottom of the base film 1. When A < 15°, the incident light is too close to parallel to the surface of the base film 1, and most of the light undergoes grazing reflection on the surface of the loose aluminum seed layer 2, making it difficult to effectively couple into the pinhole channel, thus reducing the light coupling efficiency. Simultaneously, an excessively small tilt angle increases the difference in light intensity distribution between adjacent pinholes, resulting in poor irradiation uniformity. When A > 45°, the incident light gradually approaches perpendicular incidence, the mirror reflection loss increases, the effect of improving optical coupling efficiency weakens, and the microcavity focusing effect is not obvious.

[0100] This invention arranges ultraviolet light sources at an angle of 15° to 45° and uses multiple sets of light sources staggered along the conveyor belt direction. On the one hand, the oblique incidence significantly reduces the specular reflection loss on the aluminum layer surface, allowing more incident light to couple into the pinhole channel. On the other hand, the oblique incidence increases the number of reflections of light on the inner wall of the pinhole, synergistically enhancing the microcavity focusing effect and resulting in higher effective light intensity at the base film 1 at the bottom of the pinhole. Simultaneously, the staggered arrangement of multiple light sources eliminates irradiation non-uniformity. The combined effect of these three factors allows the surface layer of the base film 1 to achieve a more complete modification effect under the same irradiation dose, further improving the elongation control effect, and potentially achieving the same elongation control target at a lower irradiation dose. This is beneficial for increasing the conveyor belt speed and reducing energy consumption.

[0101] In addition, the irradiation chamber containing the ultraviolet irradiation is filled with a mixture of oxygen and an inert gas (such as argon or nitrogen), with the oxygen volume fraction being 0.1% to 5%. Ultraviolet light excites the oxygen to generate ozone and reactive oxygen atoms, which diffuse through the pinhole structure 21 to the surface of the base film 1. This photochemical oxidation reaction assists in etching the surface layer of the base film 1, improving the modification depth and efficiency under the same light dose; or, under the same modification requirements, reducing the irradiation time to match the high-speed conveyor belt cycle of the production line. The determination of the oxygen content range of 0.1% to 5% is based on the following: below 0.1%, the oxygen content is too low, and the oxidation-assisted effect is negligible; above 5%, the surface of the loose aluminum seed layer 2 is severely oxidized, affecting the adhesion and conductivity of the subsequent dense layer, and the excessive ozone generation places excessive demands on equipment sealing and exhaust gas treatment.

[0102] During ultraviolet irradiation, ultraviolet light with wavelengths of 200nm~380nm can excite oxygen molecules to undergo photolysis, generating highly reactive ozone and reactive oxygen atoms. Ozone is a strong oxidant, and reactive oxygen atoms possess extremely high reactivity. Both can diffuse through pinhole channels to the surface of substrate film 1, performing photochemical oxidation etching on the polymer molecular chains of the substrate film 1 surface. This oxidation etching effect, combined with the molecular chain breaking / crosslinking effect of direct ultraviolet irradiation, allows for deeper modification depth (oxidation etching can extend to the subsurface region below the direct penetration depth of ultraviolet light) and a more complete degree of modification (oxidation etching increases the reaction channels for molecular chain breaking) under the same ultraviolet irradiation dose, thus significantly improving modification efficiency. Therefore, while maintaining the target elongation rate, the ultraviolet irradiation dose can be reduced or the irradiation time shortened, allowing for an increase in the production line conveyor speed and better matching the production efficiency requirements of large-scale mass production.

[0103] However, higher oxygen content is not always better. When the oxygen volume fraction is below 0.1%, the oxygen molecule concentration in the irradiation cavity is too low, and the number of ozone and active oxygen atoms generated by ultraviolet light excitation is extremely limited. Their oxidative etching effect is negligible compared to the direct irradiation effect of ultraviolet light (the improvement in modification depth and efficiency is less than 5%), and cannot make a substantial contribution to the modification effect.

[0104] When the oxygen volume fraction exceeds 5%, the excess oxygen generates a large amount of ozone and reactive oxygen atoms under ultraviolet light excitation. These highly reactive species diffuse to the surface of the base film 1 through pinholes and also react with the aluminum surface of the loose aluminum seed layer 2, forming a thicker alumina layer on the aluminum surface. The presence of this alumina layer severely degrades the interfacial bonding strength of the subsequent dense aluminum functional layer 3 (the aluminum-aluminum metal bond becomes an aluminum-alumina-aluminum physical contact, significantly reducing the bonding strength), while also increasing the interfacial contact resistance and affecting the conductivity of the composite current collector. Furthermore, the generation of excess ozone places extremely high demands on the sealing performance and exhaust gas treatment system of the vacuum evaporation equipment. The strong corrosiveness of ozone accelerates the aging of equipment seals, increasing equipment maintenance costs, while the exhaust gas treatment of high-concentration ozone also increases the environmental burden and operating costs.

[0105] Therefore, by controlling the oxygen volume fraction in the irradiation chamber within the range of 0.1% to 5%, this invention ensures, on the one hand, that there is a sufficient concentration of oxygen molecules in the irradiation chamber, enabling ultraviolet light excitation to generate sufficient ozone and active oxygen atoms. Through photochemical oxidation-assisted etching, the modification depth and efficiency are improved under the same light dose (modification efficiency is improved by 15% to 30%, or the irradiation time can be reduced by 20% to 40% under the same modification requirements), thereby providing process space for high-speed conveyor belts in production lines. On the other hand, it avoids excessive oxidation of the aluminum layer surface (thickening of the Al2O3 layer), decreased interfacial bonding, and deterioration of conductivity caused by excessive oxygen, while ensuring that the ozone generation is within the range that the equipment sealing and exhaust gas treatment systems can withstand, thus balancing process effectiveness and equipment reliability.

[0106] In step S2400, a dense aluminum functional layer 3 is formed on the surface of the loose aluminum seed layer 2 away from the base film 1, so that the dense aluminum functional layer 3 fills and covers the pinhole structure 21.

[0107] Under a vacuum environment with a second preset vacuum level, a dense aluminum functional layer 3 is deposited on the surface of the loose aluminum seed layer 2 away from the base film 1 at a second preset evaporation rate, wherein the second preset evaporation rate is v2, 1nm / s≤v2≤5nm / s. Below 1nm / s, the continuous production efficiency is too low; above 5nm / s, aluminum atom migration is insufficient, density decreases, and pinholes cannot be completely filled; controlling the evaporation rate (≤5 nm / s) ensures that aluminum atoms have sufficient time to diffuse and migrate on the surface, forming a high-density columnar crystal structure.

[0108] More specifically, the evaporation rate v2 of the dense aluminum functional layer 3 determines the diffusion and migration behavior of aluminum atoms in the dense aluminum functional layer 3 on the surface of the loose aluminum seed layer 2 and the film growth mode. When v2 is in the range of 1 nm / s to 5 nm / s, the aluminum atoms in the dense aluminum functional layer 3 have sufficient time to diffuse and migrate on the surface of the loose aluminum seed layer 2 after deposition, which can effectively enter the interior of the pinhole and fill it layer by layer from the bottom of the hole, eventually completely sealing the pinhole; at the same time, the film formed on the surface of the loose layer has a columnar crystal structure, with dense grain arrangement, few grain boundaries, low film resistivity and excellent corrosion resistance.

[0109] When the second preset evaporation rate v2 is less than 1 nm / s, although the diffusion and migration time of aluminum atoms is more sufficient and the film density is higher, the number of aluminum atoms deposited per unit time is too small, and the evaporation time required to form the target thickness (50 nm~200 nm) is significantly extended. When the second preset evaporation rate v2 is greater than 5 nm / s, the diffusion and migration time of aluminum atoms on the surface of the base film 1 is insufficient, and the atoms are covered by subsequently arriving aluminum atoms before they have found the lowest energy lattice position.

[0110] Therefore, by controlling the second preset evaporation rate v2 within the range of 1nm / s to 5nm / s, this invention ensures that aluminum atoms have sufficient time to diffuse and migrate fully on the surface of the loose aluminum seed layer 2, allowing atoms to enter the pinhole and fill it layer by layer from the bottom of the hole, completely sealing the pinhole and forming a high-density columnar crystal structure on the surface.

[0111] The thickness of the dense aluminum functional layer 3 is H2, where 50nm ≤ H2 ≤ 200nm. When H2 is less than 50 nm, it cannot completely cover the pinhole structure 21 of the loose aluminum seed layer 2 (the pinhole depth is 10~500 nm, and the thickness of the dense aluminum functional layer 3 must be greater than the thickness of the loose aluminum seed layer 2 to completely seal the pores); when H2 is greater than 200 nm, it increases the material cost and has limited effect on performance improvement. At the same time, an excessively thick dense aluminum functional layer 3 will reduce the flexibility of the composite current collector.

[0112] The second preset vacuum level C is 1×10⁻⁶. -3 ~5×10 -3 Pa. High vacuum reduces the scattering of aluminum atoms by residual gas molecules, ensuring a stable deposition rate and film density. This ensures that the dense aluminum functional layer 3 completely fills and covers the pinhole structure 21, forming a continuous, defect-free conductive layer.

[0113] Specifically, during the vacuum evaporation process, residual gas molecules (mainly water vapor, oxygen, nitrogen, etc.) in the chamber collide with aluminum atoms flying from the evaporation source towards the base film 1, altering the flight direction and kinetic energy of the aluminum atoms. The higher the concentration of residual gas molecules (the lower the vacuum level), the higher the collision frequency, the shorter the mean free path of the aluminum atoms, and the lower the energy and the more dispersed the aluminum atoms reaching the surface of the base film 1. When the second preset vacuum level C is 1×10... -3 Pa~5×10 -3 Within the Pa range, the concentration of residual gas molecules in the chamber is extremely low, and the probability of aluminum atoms colliding with residual gas molecules in their flight path is extremely low (mean free path > 50m, much greater than the distance from the evaporation source to the base film 1). Aluminum atoms can reach the surface of the base film 1 with high kinetic energy and high directionality, ensuring the stability of the deposition rate and the density of the film layer.

[0114] When the second preset vacuum degree C is higher than 5×10 -3 Pa (meaning insufficient vacuum, excessive residual gas in the chamber, absolute pressure higher than 5 × 10⁻⁶) -3 At a concentration of Pa, the residual gas molecules are high, and aluminum atoms collide frequently with them as they travel from the evaporation source to the surface of the base film 1. On one hand, the flight direction of aluminum atoms is randomly scattered, and some atoms deviate from their original deposition direction, failing to effectively reach the bottom and sidewalls of the pinholes, resulting in incomplete pinhole filling. On the other hand, aluminum atoms lose kinetic energy in collisions with residual gas molecules, resulting in insufficient energy upon reaching the surface of the base film 1, reduced surface diffusion and migration capabilities, and a looser film growth. Furthermore, oxygen molecules in the residual gas may be captured in the grown aluminum layer, forming Al2O3 inclusions, increasing the film resistivity. These factors combined lead to a decrease in the density of the dense layer, incomplete pinhole sealing, and increased surface resistivity.

[0115] The second preset vacuum level is less than 1×10⁻⁶. -3 Pa (i.e., vacuum is too high, absolute pressure is less than 1×10⁻⁶) -3 At a density of 1 × 10⁻⁶ Pa, although the film density may be further improved, the requirements for the vacuum pumping system are significantly increased. -3 Ultra-high vacuum below Pa requires longer evacuation times, higher-performance vacuum pump sets, and more stringent chamber sealing conditions, significantly increasing equipment investment and operating energy consumption. Furthermore, the extended evacuation time reduces production line efficiency. Simultaneously, under a given aluminum atom deposition rate, the improvement in film density from excessively high vacuum levels has reached saturation (the effect of residual gas scattering is negligible), and further reducing the vacuum level yields extremely limited performance gains, resulting in a severe imbalance with the substantial increase in equipment costs.

[0116] Therefore, the present invention controls the second preset vacuum degree to 1×10 -3Pa~5×10 -3 Within the Pa range, on the one hand, the concentration of residual gas molecules in the chamber is ensured to be low enough, the collision frequency of aluminum atoms with residual gas molecules in the flight path is controllable and the scattering effect is negligible, and aluminum atoms can reach the surface of the base film 1 with high kinetic energy and high directionality and fully migrate and diffuse to form a high-density columnar crystal structure, ensuring that the pinholes are completely filled and covered.

[0117] It is also worth noting that the first preset vacuum level and the second preset vacuum level are set completely differently in this invention. The two values ​​differ by an order of magnitude, reflecting the process logic shift from "utilizing defects" (forming pinhole structures 21 under low vacuum) to "eliminating defects" (completely sealing pores under high vacuum). This is an indispensable differentiated control method in the three-step design of "loose layer - ultraviolet irradiation - dense layer" in this invention.

[0118] First preset vacuum degree B (1×10) -2 Pa~5×10 -2 A vacuum of 250 Pa is used to vapor-deposit a loose aluminum seed layer 2. At this point, residual gas molecules are needed to assist in forming a pinhole structure 21. A suitable vacuum level ensures a moderate concentration of residual gas molecules within the chamber. During their flight, aluminum atoms collide moderately with these residual gas molecules, disturbing their flight direction and kinetic energy. These molecules are then trapped during aluminum layer growth, forming bubbles or voids, ultimately resulting in a uniform and controllable pinhole structure 21. This is precisely the "natural micromask" upon which the subsequent ultraviolet targeted irradiation of this invention relies. If the vacuum level is too high (B < 1 × 10⁻⁶), the vacuum will be insufficient. -2 Pa), the residual gas is extremely scarce, making pinholes difficult to form; if the vacuum is too low (B > 5 × 10 Pa), the residual gas is extremely rare, and pinholes are difficult to form; -2 Excessive residual gas leads to uncontrolled pinhole structure 21 and poor film uniformity.

[0119] Second preset vacuum degree C (1×10) -3 Pa~5×10 -3 (Pa) is used for evaporating a dense aluminum functional layer 3. At this point, it is necessary to eliminate the interference of residual gas on aluminum atom deposition to ensure the quality of the dense layer. The high vacuum environment results in an extremely low concentration of residual gas molecules. Aluminum atoms hardly collide with residual gas molecules during their flight path, allowing them to reach the surface of the base film 1 with high kinetic energy and high directionality and fully diffuse and migrate, forming a high-density columnar crystal structure. This ensures that pinholes are completely filled and covered, forming a continuous, defect-free conductive layer. If the vacuum level is insufficient (C > 5 × 10⁻⁶), the deposition of the dense aluminum functional layer 3 will be affected. -3 Pa), residual gas scattering leads to incomplete pinhole filling and a loose film layer; if an excessively high vacuum degree is pursued (C < 1 × 10), it will result in incomplete pinhole filling and a loose film layer. -3 Pa), equipment costs rise sharply and performance gains are limited.

[0120] Example 1

[0121] S1. A 6μm thick PET base film 1 is selected. The initial elongation at break of the base film 1 is 120%, and the initial tensile strength is 210MPa. The surface of the base film 1 to be coated with aluminum is subjected to plasma cleaning treatment with a power of 300 W and a treatment time of 30s.

[0122] S2, the pretreated base film 1 is fed into the first vapor deposition chamber of the vacuum winding vapor deposition equipment, under a first preset vacuum degree of 3×10 -2 Under Pa conditions, a loose aluminum seed layer 2 was deposited at a high evaporation rate of 10 nm / s, with a thickness H1 of 100 nm. The porosity P of the resulting loose aluminum seed layer 2 was 18%, and the diameter D of the pinhole structure 21 was 1.2 μm. This data was obtained from statistical analysis of SEM images, with a statistical count of 100 pinhole structures 21, and H1 / D was approximately 0.83:1.

[0123] S3, the semi-finished product coated with the loose aluminum seed layer 2 is placed into the ultraviolet irradiation chamber. Under an air atmosphere, the side of the base film 1 coated with the loose aluminum seed layer 2 is irradiated with ultraviolet light of wavelength 365nm. The irradiation dose is controlled at 100mJ / cm. 2 The ultraviolet light source is incident perpendicularly, that is, at a 90° angle to the traveling plane of the base film 1.

[0124] S4, the irradiated semi-finished product is sent into the second evaporation chamber, where the second preset vacuum degree is 3×10 -3 Under Pa conditions, a dense aluminum functional layer 3 was deposited at a low evaporation rate of 3 nm / s, with the layer thickness controlled to be 120 nm.

[0125] Example 2

[0126] S1. A 6μm thick PET base film 1 is selected. The initial elongation at break of the base film 1 is 120%, and the initial tensile strength is 210MPa. The surface of the base film 1 to be coated with aluminum is subjected to plasma cleaning treatment with a treatment power of 300W and a treatment time of 30s.

[0127] S2, the pretreated base film 1 is fed into the first vapor deposition chamber of the vacuum winding vapor deposition equipment, under a first preset vacuum degree of 3×10 -2 Under Pa conditions, a loose aluminum seed layer 2 was deposited at a high evaporation rate of 12 nm / s, with a thickness H1 of 150 nm. The porosity P of the resulting loose aluminum seed layer 2 was 28%, and the diameter D of the pinhole structure 21 was 2.5 μm. This data was obtained from statistical analysis of SEM images, with a statistical count of 100 pinhole structures 21, and H1 / D was approximately 0.6:1.

[0128] S3. The semi-finished product coated with a loose aluminum layer is placed into an ultraviolet irradiation chamber. Under an air atmosphere, the side of the base film 1 coated with the loose aluminum seed layer 2 is irradiated with ultraviolet light of wavelength 310nm. The irradiation dose is controlled at 250mJ / cm². 2 The ultraviolet light source is incident perpendicularly.

[0129] S4, the irradiated semi-finished product is sent into the second evaporation chamber, where the second preset vacuum degree is 3×10 -3 Under Pa conditions, a dense aluminum functional layer 3 was deposited at a low evaporation rate of 3 nm / s, with the layer thickness controlled to be 160 nm.

[0130] Example 3 (Preferred Example with High Modification) S1. A 6μm thick PET base film 1 is selected. The initial elongation at break of the base film 1 is 120%, and the initial tensile strength is 210MPa. The surface of the base film 1 to be coated with aluminum is subjected to plasma cleaning treatment with a treatment power of 300W and a treatment time of 30s.

[0131] S2, the pretreated base film 1 is fed into the first vapor deposition chamber of the vacuum winding vapor deposition equipment, under a first preset vacuum degree of 3×10 -2 Under Pa conditions, a loose aluminum seed layer 2 was deposited at a high evaporation rate of 14 nm / s, with a thickness H1 of 180 nm. The porosity P of the resulting loose aluminum seed layer 2 was 38%, and the diameter D of the pinhole structure 21 was 4.0 μm. This data was obtained through statistical analysis of SEM images, with a statistical count of 100 pinhole structures 21, and H1 / D was approximately 0.45:1.

[0132] S3. The semi-finished product coated with a loose aluminum layer is placed into an ultraviolet irradiation chamber. Under an air atmosphere, the side of the base film 1 coated with the loose aluminum seed layer 2 is irradiated with ultraviolet light of wavelength 254nm. The irradiation dose is controlled at 450mJ / cm². 2 The ultraviolet light source is incident perpendicularly.

[0133] S4, the irradiated semi-finished product is sent into the second evaporation chamber, where the second preset vacuum degree is 3×10 -3 Under Pa conditions, a dense aluminum functional layer 3 was deposited at a low evaporation rate of 3 nm / s, with the layer thickness controlled to be 200 nm.

[0134] Example 4

[0135] S1. A 6μm thick PET base film 1 is selected. The initial elongation at break of the base film 1 is 120%, and the initial tensile strength is 210MPa. The surface of the base film 1 to be coated with aluminum is subjected to plasma cleaning treatment with a power of 300 W and a treatment time of 30s.

[0136] S2, the pretreated base film 1 is fed into the first vapor deposition chamber of the vacuum winding vapor deposition equipment, under a first preset vacuum degree of 3×10 -2 Under Pa conditions, a loose aluminum seed layer 2 was deposited at a high-speed evaporation rate of 12 nm / s, and the thickness H1 of the loose aluminum seed layer 2 was 150 nm. The porosity P of the obtained loose aluminum seed layer 2 was 28%, and the diameter D of the pinhole structure 21 was 2.5 μm. After the loose aluminum seed layer 2 is prepared, low-pressure argon plasma is introduced online to roughen the surface of the loose aluminum seed layer 2. The treatment power is 150 W and the treatment time is 10 s.

[0137] S3. The roughened semi-finished product is sent into an ultraviolet irradiation chamber. A mixed atmosphere of oxygen and argon with a volume fraction of 2% is introduced into the irradiation chamber. Ultraviolet light with a wavelength of 310nm is used to irradiate the side of the base film 1 with the loose aluminum seed layer 2. The irradiation dose is controlled at 180mJ / cm. 2 The ultraviolet light source is arranged at a 30° angle to the plane of the substrate film 1, and two sets of light sources are arranged alternately along the direction of the substrate.

[0138] S4, the irradiated semi-finished product is sent into the second evaporation chamber, under a second preset vacuum degree of 3×10 -3 Under Pa conditions, a dense aluminum functional layer 3 was deposited at a low evaporation rate of 3 nm / s, with the layer thickness controlled to be 160 nm.

[0139] Example 5

[0140] S1. A 6μm thick PET base film 1 is selected. The initial elongation at break of the base film 1 is 120%, and the initial tensile strength is 210MPa. The surface of the base film 1 to be coated with aluminum is subjected to plasma cleaning treatment with a power of 300 W and a treatment time of 30s.

[0141] S2, the pretreated base film 1 is fed into the first vapor deposition chamber of the vacuum winding vapor deposition equipment, under a first preset vacuum degree of 3×10 -2 Under Pa conditions, a loose aluminum seed layer 2 was deposited at a high evaporation rate of 12 nm / s, and the thickness H1 of the loose aluminum seed layer 2 was 150 nm. The porosity P of the obtained loose aluminum seed layer 2 was 28%, and the diameter D of the pinhole structure 21 was 2.5 μm. After the loose aluminum seed layer 2 is prepared, low-pressure argon plasma is introduced online to roughen the surface of the loose aluminum seed layer 2. The treatment power is 150 W and the treatment time is 10 s.

[0142] S3. The roughened semi-finished product is sent into the ultraviolet irradiation chamber. Under air atmosphere, the side of the base film 1 with the loose aluminum seed layer 2 is irradiated with ultraviolet light of wavelength 310nm. The irradiation dose is controlled at 250mJ / cm².2 The ultraviolet light source is incident perpendicularly.

[0143] S4, the irradiated semi-finished product is sent into the second evaporation chamber, where the second preset vacuum degree is 3×10 -3 Under Pa conditions, a dense aluminum functional layer 3 was deposited at a low evaporation rate of 3 nm / s, with the layer thickness controlled to be 160 nm.

[0144] Example 6

[0145] S1. A 6μm thick PET base film 1 is selected. The initial elongation at break of the base film 1 is 120%, and the initial tensile strength is 210MPa. The surface of the base film 1 to be coated with aluminum is subjected to plasma cleaning treatment with a power of 300 W and a treatment time of 30s.

[0146] S2, the pretreated base film 1 is fed into the first vapor deposition chamber of the vacuum winding vapor deposition equipment, under a first preset vacuum degree of 3×10 -2 Under Pa conditions, a loose aluminum seed layer 2 was deposited at a high-speed evaporation rate of 12 nm / s, and the thickness H1 of the loose aluminum seed layer 2 was 150 nm. The porosity P of the obtained loose aluminum seed layer 2 was 28%, and the diameter D of the pinhole structure 21 was 2.5 μm.

[0147] S3, the semi-finished product coated with the loose aluminum seed layer 2 is placed into the ultraviolet irradiation chamber. Under an air atmosphere, the side of the base film 1 coated with the loose aluminum seed layer 2 is irradiated with ultraviolet light of wavelength 310nm. The irradiation dose is controlled at 200mJ / cm. 2 The ultraviolet light source is arranged at a 30° angle to the plane of the substrate film 1, and two sets of light sources are arranged alternately along the direction of the substrate.

[0148] S4, the irradiated semi-finished product is sent into the second evaporation chamber, where the second preset vacuum degree is 3×10 -3 Under Pa conditions, a dense aluminum functional layer 3 was deposited at a low evaporation rate of 3 nm / s, with the layer thickness controlled to be 160 nm.

[0149] Example 7

[0150] S1. A 6μm thick PET base film 1 is selected. The initial elongation at break of the base film 1 is 120%, and the initial tensile strength is 210MPa. The surface of the base film 1 to be coated with aluminum is subjected to plasma cleaning treatment with a power of 300 W and a treatment time of 30s.

[0151] S2, the pretreated base film 1 is fed into the first vapor deposition chamber of the vacuum winding vapor deposition equipment, under a first preset vacuum degree of 3×10 -2Under Pa conditions, a loose aluminum seed layer 2 was deposited at a high-speed evaporation rate of 12 nm / s, and the thickness H1 of the loose aluminum seed layer 2 was 150 nm. The porosity P of the obtained loose aluminum seed layer 2 was 28%, and the diameter D of the pinhole structure 21 was 2.5 μm.

[0152] S3, the semi-finished product coated with the loose aluminum seed layer 2 is placed into the ultraviolet irradiation chamber. The irradiation chamber is filled with a mixed atmosphere of oxygen and argon with a volume fraction of 2%. The side of the base film 1 coated with the loose aluminum seed layer 2 is irradiated with ultraviolet light with a wavelength of 310nm. The irradiation dose is controlled at 200mJ / cm. 2 The ultraviolet light source is incident perpendicularly.

[0153] S4, the irradiated semi-finished product is sent into the second evaporation chamber, where the second preset vacuum degree is 3×10 -3 Under Pa conditions, a dense aluminum functional layer 3 was deposited at a low evaporation rate of 3 nm / s, with the layer thickness controlled to be 160 nm.

[0154] Example 8

[0155] S1. A 6μm thick PET base film 1 is selected. The initial elongation at break of the base film 1 is 120%, and the initial tensile strength is 210MPa. The surface of the base film 1 to be coated with aluminum is subjected to plasma cleaning treatment with a power of 300 W and a treatment time of 30s.

[0156] S2, the pretreated base film 1 is fed into the first vapor deposition chamber of the vacuum winding vapor deposition equipment, under a first preset vacuum degree of 3×10 -2 Under Pa conditions, a loose aluminum seed layer 2 was deposited at a high evaporation rate of 12 nm / s, with a thickness H1 of 400 nm. The porosity P of the resulting loose aluminum seed layer 2 was 26%, and the diameter D of the pinhole structure 21 was 1.5 μm. This data was obtained from statistical analysis of SEM images, with a statistical count of 100 pinhole structures 21, and H1 / D was approximately 2.67:1.

[0157] S3, the semi-finished product coated with the loose aluminum seed layer 2 is placed into the ultraviolet irradiation chamber. Under an air atmosphere, the side of the base film 1 coated with the loose aluminum seed layer 2 is irradiated with ultraviolet light of wavelength 310nm. The irradiation dose is controlled at 400mJ / cm. 2 The ultraviolet light source is incident perpendicularly.

[0158] S4, the irradiated semi-finished product is sent into the second evaporation chamber, where the second preset vacuum degree is 3×10 -3 Under Pa conditions, a dense aluminum functional layer 3 was deposited at a low evaporation rate of 3 nm / s, with the layer thickness controlled to be 420 nm.

[0159] Example 9

[0160] S1. A 6μm thick PET base film 1 is selected. The initial elongation at break of the base film 1 is 120%, and the initial tensile strength is 210MPa. The surface of the base film 1 to be coated with aluminum is subjected to plasma cleaning treatment with a power of 300 W and a treatment time of 30s.

[0161] S2, the pretreated base film 1 is fed into the first vapor deposition chamber of the vacuum winding vapor deposition equipment, under a first preset vacuum degree of 3×10 -2 Under Pa conditions, a loose aluminum seed layer 2 was deposited at a high evaporation rate of 12 nm / s, and the thickness H1 of the loose aluminum seed layer 2 was 150 nm. The porosity P of the obtained loose aluminum seed layer 2 was 28%, and the diameter D of the pinhole structure 21 was 2.5 μm.

[0162] S3, the semi-finished product coated with the loose aluminum seed layer 2 is placed into the ultraviolet irradiation chamber. Under an air atmosphere, the side of the base film 1 coated with the loose aluminum seed layer 2 is irradiated with ultraviolet light of wavelength 365nm. The irradiation dose is controlled at 250mJ / cm. 2 The ultraviolet light source is incident perpendicularly.

[0163] S4, the irradiated semi-finished product is sent into the second evaporation chamber, where the second preset vacuum degree is 3×10 -3 Under Pa conditions, a dense aluminum functional layer 3 was deposited at a low evaporation rate of 3 nm / s, with the layer thickness controlled to be 160 nm.

[0164] Example 10

[0165] S1. A 6μm thick PET base film 1 is selected. The initial elongation at break of the base film 1 is 120%, and the initial tensile strength is 210MPa. The surface of the base film 1 to be coated with aluminum is subjected to plasma cleaning treatment with a power of 300 W and a treatment time of 30s.

[0166] S2, the pretreated base film 1 is fed into the first vapor deposition chamber of the vacuum winding vapor deposition equipment, under a first preset vacuum degree of 3×10 -2 Under Pa conditions, a loose aluminum seed layer 2 was deposited at a high evaporation rate of 12 nm / s. The thickness H1 of the loose aluminum seed layer 2 was 150 nm. The porosity P of the obtained loose aluminum seed layer 2 was 28%, and the diameter D of the pinhole structure 21 was 2.5 μm.

[0167] S3, the semi-finished product coated with the loose aluminum seed layer 2 is placed into the ultraviolet irradiation chamber. Under an air atmosphere, the side of the base film 1 coated with the loose aluminum seed layer 2 is irradiated with ultraviolet light of wavelength 310nm. The irradiation dose is controlled at 80mJ / cm. 2 The ultraviolet light source is incident perpendicularly.

[0168] S4, the irradiated semi-finished product is sent into the second evaporation chamber, where the second preset vacuum degree is 3×10 -3 Under Pa conditions, a dense aluminum functional layer 3 was deposited at a low evaporation rate of 3 nm / s, with the layer thickness controlled to be 160 nm.

[0169] Example 11

[0170] S1. A PET base film 1 with a thickness of 15 μm is selected. The initial elongation at break of the base film 1 is 135%, and the initial tensile strength is 195 MPa. The surface of the base film 1 to be coated with aluminum is subjected to plasma cleaning treatment with a treatment power of 300 W and a treatment time of 30 s.

[0171] S2, the pretreated base film 1 is fed into the first vapor deposition chamber of the vacuum winding vapor deposition equipment, under a first preset vacuum degree of 3×10 -2 Under Pa conditions, a loose aluminum seed layer 2 was deposited at a high evaporation rate of 12 nm / s, with a thickness H1 of 150 nm. The resulting loose aluminum seed layer 2 had a porosity P of 28% and a pinhole structure 21 diameter D of 2.5 μm.

[0172] S3, the semi-finished product coated with the loose aluminum seed layer 2 is placed into the ultraviolet irradiation chamber. Under an air atmosphere, the side of the base film 1 coated with the loose aluminum seed layer 2 is irradiated with ultraviolet light of wavelength 310nm. The irradiation dose is controlled at 250mJ / cm. 2 The ultraviolet light source is incident perpendicularly.

[0173] S4, the irradiated semi-finished product is sent into the second evaporation chamber, under a vacuum of 3×10⁻⁶. -3 Under Pa conditions, a dense aluminum functional layer 3 was deposited at a low evaporation rate of 3 nm / s, with the layer thickness controlled to be 160 nm.

[0174] Comparative Example 1 A 6 μm thick PET base film 1 was selected. This base film 1 had an initial elongation at break of 120% and an initial tensile strength of 210 MPa. Without any UV irradiation treatment, the base film 1 was directly deposited at a low evaporation rate of 3 nm / s under a vacuum of 3 × 10⁻⁶ MPa. - 3 A dense aluminum layer of 200 nm was deposited under Pa conditions.

[0175] Comparative Example 2 This comparative example represents a full-surface ultraviolet irradiation scheme in the prior art.

[0176] A PET base film 1 with a thickness of 6 μm was selected. The initial elongation at break of the base film 1 was 120%, and the initial tensile strength was 210 MPa. The surface of the base film 1 was subjected to plasma cleaning treatment.

[0177] The base film 1 was directly placed into the ultraviolet irradiation chamber without undergoing the step of depositing a loose aluminum layer. Under an air atmosphere, the entire surface of the base film 1 was irradiated with ultraviolet light at a wavelength of 310 nm, and the irradiation dose was controlled at 250 mJ / cm². 2 .

[0178] The irradiated base film 1 was sent into the evaporation chamber under a vacuum of 3×10⁻⁶. -3 Under Pa conditions, a 200 nm dense aluminum layer was deposited at a low evaporation rate of 3 nm / s.

[0179] Comparative Example 3 This comparative example is a scheme where the process order is reversed, with a dense layer deposited first and then subjected to ultraviolet irradiation.

[0180] A 6μm thick PET base film 1 was selected, with an initial elongation at break of 120% and an initial tensile strength of 210MPa. The surface of the base film 1 to be coated with aluminum was subjected to plasma cleaning treatment.

[0181] The pretreated base film 1 was sent into the evaporation chamber and deposited under a vacuum of 3×10⁻⁶. -3 Under Pa conditions, a 200 nm dense aluminum layer was deposited at a low evaporation rate of 3 nm / s.

[0182] The semi-finished product coated with a dense aluminum layer is placed into an ultraviolet irradiation chamber. Under an air atmosphere, the aluminum-coated surface is irradiated with ultraviolet light at a wavelength of 310 nm on one side, with the irradiation dose controlled at 250 mJ / cm². 2 .

[0183] Test methods The performance tests of the composite aluminum current collectors obtained in the following embodiments and comparative examples were all conducted according to the test methods and equipment described below.

[0184] (1) Elongation at break test: The test was conducted using a universal tensile testing machine with a sample width of 15 mm, a gauge length of 50 mm, a tensile rate of 50 mm / min, and an electronic universal testing machine.

[0185] (2) Tensile strength test: The same test method and equipment as the elongation at break were used. The sample width was 15 mm, the gauge length was 50 mm, and the tensile rate was 50 mm / min.

[0186] (3) Tensile strength retention rate: calculated by dividing the modified tensile strength by the tensile strength of the unmodified base film 1 and then multiplying by 100%.

[0187] (4) Surface resistance test: The four-probe method is used for testing, and the testing equipment is a four-probe resistance tester.

[0188] (5) Porosity test: The porosity was obtained by image analysis and binarization of the SEM cross-sectional image. The test equipment was a field emission scanning electron microscope.

[0189] (6) Pinhole equivalent diameter test: Statistical analysis was performed using SEM images. At least 100 pinholes were counted for each sample. The testing equipment was a field emission scanning electron microscope.

[0190] (7) Aluminum layer thickness test: The thickness was obtained by direct measurement using SEM cross-section. The testing equipment was a field emission scanning electron microscope.

[0191] (8) Electrolyte corrosion resistance test: Immerse the sample in an electrolyte with a volume ratio of 1 mol / L LiPF6 / EC+DEC of 1:1 and place it at 60℃ for 72 hours. Observe the appearance changes and test the surface resistance change rate. The test equipment is a constant temperature oven with a four-probe resistance tester.

[0192] Table 1 Comparison of the first test data of the embodiments and comparative examples.

[0193] Table 2 Comparison of the second test data of the embodiments and comparative examples.

[0194] As can be seen from the comparison between the examples and the comparative examples, the technical solution of the present invention achieves a balance between elongation control and strength retention that is impossible to achieve with existing technologies. Specifically, this is reflected in the following aspects: The unmodified PET base film 1 of Comparative Example 1 has a breaking elongation of 115% and a tensile strength of 208 MPa. Examples 1 to 3 reduce the elongation to 38%, 27%, and 14%, respectively, while the tensile strength remains at 198 MPa, 185 MPa, and 172 MPa, with tensile strength retention rates as high as 94.3%, 88.1%, and 81.9%. This indicates that the present invention, through pinhole masking and targeted ultraviolet irradiation, achieves a significant reduction in elongation at the expense of moderate strength, thus solving the problem of deformation during coating and baking.

[0195] Furthermore, the whole-area irradiation dose of Comparative Example 2 was 250 mJ / cm². 2 The elongation decreased to 25%, but the tensile strength retention was only 65.7%. In contrast, Example 2, under the same dosage and base film 1 conditions, had an elongation of 27% (similar level) and a tensile strength retention as high as 88.1%, which was 22.4 percentage points higher than Comparative Example 2; Example 3, at 450 mJ / cm 2 The elongation rate further decreased to 14% under the dose (far lower than Comparative Example 2), while the strength retention rate still reached 81.9%, which proves that the discrete point damage mechanism effectively avoids the destructive degradation of the entire base film 1 by whole-area irradiation.

[0196] Furthermore, in Comparative Example 3, since a dense layer was deposited first and then subjected to ultraviolet irradiation, the dense layer had no pinhole structure 21, and ultraviolet light could not penetrate the aluminum layer. The elongation was still as high as 108%, which was almost equivalent to the unmodified base film 1. This fully demonstrates that the pinhole structure 21 of the loose aluminum seed layer 2 is a necessary condition for ultraviolet light to penetrate the aluminum layer and achieve modification of the base film 1.

[0197] Furthermore, the above embodiments and comparative examples further verified that 0.5μm≤D≤5μm, 10nm≤H1≤500nm, 15%≤P≤40%; 200nm≤L≤380nm, and 50mJ / cm 2 ≤S≤500mJ / cm 2 The best results are achieved when the whole is combined.

[0198] The present invention also provides an electrode comprising the above-described composite aluminum current collector or a composite aluminum current collector prepared by the above-described preparation method. Embodiments of the electrode provided by the present invention include embodiments comprising the above-described composite aluminum current collector or embodiments comprising the above-described preparation method; the beneficial effects of the above-described composite aluminum current collector and the beneficial effects of the above-described preparation method can be applied to the electrode.

[0199] The present invention also provides an electrochemical device comprising the aforementioned electrode. Embodiments of this electrochemical device include embodiments of the aforementioned electrode, and the beneficial effects of the aforementioned electrode can be applied to the electrochemical device.

[0200] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A composite aluminum current collector, characterized in that, include: Base film; A loose aluminum seed layer is disposed on at least one side surface of the base film. The loose aluminum seed layer has a plurality of pinhole structures penetrating along the thickness direction. The porosity of the loose aluminum seed layer is P, where 15% ≤ P ≤ 40%. A dense aluminum functional layer is disposed on the side surface of the loose aluminum seed layer away from the base film, and fills and covers the pinhole structure; The base film has discrete point-like damage regions at positions corresponding to the pinhole structures, and the polymer molecular chains of the base film are damaged in these discrete point-like damage regions.

2. The composite aluminum current collector as described in claim 1, characterized in that, The pore size of the pinhole structure is D, and the thickness of the loose aluminum seed layer is H1, where 0.5:1≤H1 / D≤2:

1.

3. The composite aluminum current collector as described in claim 2, characterized in that, The thickness of the dense aluminum functional layer is H2, 50nm≤H2≤200nm; And / or, 0.5μm≤D≤5μm; And / or, 10nm≤H1≤500nm.

4. The composite aluminum current collector as described in claim 1, characterized in that, The base film is made of one or more of polyethylene terephthalate, polyimide, polypropylene, and polybutylene terephthalate. And / or, The thickness of the base film is H3, where 4μm≤H3≤12μm.

5. The composite aluminum current collector as described in claim 1, characterized in that, The loose aluminum seed layer has a gradient pore structure along the thickness direction. The loose aluminum seed layer includes a bottom layer close to the base film and an upper layer connected to the bottom layer. The porosity of the bottom layer is greater than that of the upper layer, and the pore size of the pinhole structure in the bottom layer is greater than that of the pinhole structure in the upper layer. Wherein, the thickness of the upper layer accounts for 60%-70% of the thickness of the loose aluminum seed layer; and / or, the pore size of the pinhole structure located in the bottom layer is D1, and the pore size of the pinhole structure located in the upper layer is D2, 0.8μm≤D1≤6μm, 0.3μm≤D2≤2μm.

6. A method for preparing a composite aluminum current collector, characterized in that, include: Provide base film; A loose aluminum seed layer is formed on at least one surface of the base film. The loose aluminum seed layer has a plurality of pinhole structures penetrating along the thickness direction. The porosity of the loose aluminum seed layer is P, where 15% ≤ P ≤ 40%. The base film with the loose aluminum seed layer is irradiated with ultraviolet light. The ultraviolet light passes through the pinhole structure and irradiates the surface of the base film, causing discrete point-like damage areas to be formed on the surface of the base film corresponding to the position of the pinhole structure. The polymer molecular chains in the discrete point-like damage areas are damaged. A dense aluminum functional layer is formed on the surface of the loose aluminum seed layer away from the base film, so that the dense aluminum functional layer fills and covers the pinhole structure.

7. The method for preparing the composite aluminum current collector as described in claim 6, characterized in that, The formation of a loose aluminum seed layer on at least one side surface of the base film includes: In a vacuum environment with a first preset vacuum level, a loose aluminum seed layer is formed on at least one side surface of the base film by evaporation at a first preset evaporation rate, so that the loose aluminum seed layer forms the pinhole structure, and the first preset evaporation rate is v1, 8nm / s≤v1≤15nm / s; And / or, 0.5:1≤H1 / D≤2:1; And / or, the pore size of the pinhole structure is D, the thickness of the loose aluminum seed layer is H1, 0.5μm≤D≤5μm, 10nm≤H1≤500nm; And / or, the loose aluminum seed layer has a gradient pore structure along the thickness direction, the loose aluminum seed layer includes a bottom layer close to the base film and an upper layer connected to the bottom layer, the porosity of the bottom layer is greater than the porosity of the upper layer, the pore size of the pinhole structure located in the bottom layer is greater than the pore size of the pinhole structure located in the upper layer, the thickness of the upper layer accounts for 60%-70% of the thickness of the loose aluminum seed layer, the pore size of the pinhole structure located in the bottom layer is D1, the pore size of the pinhole structure located in the upper layer is D2, 0.8μm≤D1≤6μm, 0.3μm≤D2≤2μm; And / or, the wavelength of the ultraviolet light is L, the irradiation dose is S, 200nm≤L≤380nm, and 50mJ / cm². 2 ≤S≤500mJ / cm 2 .

8. The method for preparing the composite aluminum current collector as described in claim 6, characterized in that, In the step of irradiating the base film with the loose aluminum seed layer using ultraviolet light, wherein the ultraviolet light passes through the pinhole structure to irradiate the surface of the base film, the ultraviolet light includes deep ultraviolet light and near ultraviolet light, wherein the wavelength of the deep ultraviolet light is L1, the wavelength of the near ultraviolet light is L2, 200nm≤L≤280nm, 315nm≤L≤380nm; and / or, the ultraviolet light is set at a preset tilt angle with the transport plane of the base film, and multiple sets of ultraviolet light sources are provided, which are staggered along the transport direction of the base film, wherein the preset tilt angle is A, 15°≤A≤45°; and / or, a mixture of oxygen and inert gas is introduced into the irradiation cavity where the ultraviolet light is irradiated, wherein the volume fraction of oxygen is 0.1%-5%; And / or, The step of forming a dense aluminum functional layer on the surface of the loose aluminum seed layer away from the base film includes: In a vacuum environment with a second preset vacuum level, a dense aluminum functional layer is deposited on the surface of the loose aluminum seed layer away from the base film at a second preset evaporation rate, wherein the second preset evaporation rate is v2, 1nm / s≤v2≤5nm / s; And / or, The thickness of the dense aluminum functional layer is H2, where 50nm ≤ H2 ≤ 200nm.

9. An electrode sheet, characterized in that, The composite aluminum current collector includes the composite aluminum current collector according to any one of claims 1-5 or the composite aluminum current collector prepared by the preparation method according to any one of claims 6-8.

10. An electrochemical device, characterized in that, Includes the electrode sheet as described in claim 9.